Free ammonia-driven sewage sludge valorization: from in-situ pretreatment to energy and resource recovery - Jiamin Zhang; Qiuxiang Xu; Yingqun Ma; Esaïe Kouadio Appiah Kouassi; Kouassi Benjamin Yao; Patrick Drogui; Rajeshwar D. Tyagi; Dongbo Wang; Jonathan W.C. Wong (Bioresource Technology, 2027)

Oral Language Skills of Children and Adolescents with Neurofibromatosis Type 1: a Systematic Review and Meta-analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Heather L. Thompson; Xian Wu; Julia Moreira; Lauren Morey; Michael Peper; Hannah Iroff; Benjamin F. Mujica; Yang Hou (Neuropsychology Review, 2026)

Mapping the lithium supply chain from mine to battery at the facility level - Luke Cullen; Baptiste Andrieu; Caio Bezerra; Benjamin Adams; Scott Jeen; André Cabrera Serrenho; Jonathan M. Cullen (Resources, Conservation and Recycling, 2026)

Corrigendum to “Deep learning error post-processing improves stochastic watershed modeling” [J. Hydrol. 675 (2026) 135663] - Benjamin Manoli; Sandeep Poudel; David K. Koval; Sarah Y. Murphy; Scott Steinschneider; Jonathan Lamontagne (Journal of Hydrology, 2026)

Deep learning error post-processing improves stochastic watershed modeling - Benjamin Manoli; Sandeep Poudel; David K. Koval; Sarah Y. Murphy; Scott Steinschneider; Jonathan Lamontagne (Journal of Hydrology, 2026)

Multi‐Model Ensembles in Ecosystem Modeling: Challenges and Best Practices for Decision‐Making - Kaiyu Guan; Rongzhu Qin; Zewei Ma; Lei Zhao; Licheng Liu; Sheng Wang; Trevor F. Keenan; Mengqi Jia; Debjani Sihi; Eric Potash; Senthold Asseng; Jingyun Tang; et al. (Global Change Biology, 2026)
Ecosystem models are increasingly central to the decision‐making for environmental policy, conservation planning, and climate‐related investments. Yet, the growing reliance on Multi‐Model Ensembles (MMEs) of ecosystem models by practitioners and policymakers, sometimes under tight timelines and imperfect information, has frequently outpaced the scientific rigor required to ensure ensemble reliability. Here, MMEs refer to approaches that combine targeted predictions from multiple models with the expectation of improving robustness and quantifying predictive uncertainty. Poorly designed MMEs may create a false sense of confidence and lead to suboptimal policy and market decisions. This perspective argues that robust decision‐making‐relevant MMEs must be grounded on two pillars: (1) rigorous Model Intercomparison Projects (MIPs), which identify inter‐model agreement and disagreement, characterize model uncertainties, and evaluate robustness with observationally based benchmarks—MIPs' diagnostic evaluation is so critical that it must be needed to drive MME's decision in model selection and weighting, especially when only a limited number of models available; and (2) co‐design by both stakeholders and scientists to ensure that scenarios, metrics and uncertainty requirements provide decision‐relevant information. Building upon the past success and lessons from the existing MIPs‐MMEs efforts (e.g., climate/Earth system/crop), we derived the theoretical basis for MMEs, addressed their specific challenges in ecosystem modeling, and highlighted proper consideration of model numbers and diversity, risk of model inter‐dependence, effective calibration of model parameters, possible overdue of some ecosystem model development, critical roles of open benchmark data across a wide range of conditions, and suggested use of Artificial Intelligence to support MIPs‐MMEs. We highlighted the under‐recognized opportunity for MIPs and MMEs to drive scientific progress and innovation through identifying better performing models, systematic benchmarking, feedback loops, and targeted model improvement. By following actionable best practice guidelines, MMEs can evolve from ad hoc aggregation of models into a trusted backbone of environmental policy and decision‐making.

The potential impact of microplastic contamination in cow manure on maternal dung burying behavior and larval survival in the dung beetle Onthophagus taurus - Nathan J. McConnell; Jaydon Galindo Lovell; Jill Walker; Benjamin J. Mathews; Scott G. Morton; Jonathan B. Shurin; Patrick T. Rohner (Chemosphere, 2026)

Psychometric framework for coexistence with large carnivores - Benjamin Ghasemi; Gerard Kyle; Tara Teel; Rebeca Niemiec; Kevin Crooks; Jenny Anne Glikman; Neil H. Carter; John A. Vucetich; Michelle L. Lute; Stewart Breck; Beatrice Frank; Dana Hoag; et al. (Conservation Biology, 2026)
Human–carnivore coexistence is essential for biodiversity conservation, yet measuring the attitudes and behaviors that support it remains methodologically challenging. We developed psychometric scales to assess willingness to coexist with carnivores and the underlying beliefs of this coexistence through an iterative expert elicitation process grounded in risk perception theory and moral psychology to ensure strong content validity. The scales measure willingness to coexist and encompass individual and collective behaviors and their cognitive antecedents: perceived positive consequences, perceived negative consequences, and ethical considerations. We validated the scales based on three representative samples of Colorado residents ( n = 434, 442, 433) focused on gray wolves ( Canis lupus ), mountain lions ( Puma concolor ), and black bears ( Ursus americanus ). Validation involved expert review, cognitive interviews, confirmatory factor analyses, and measurement invariance testing across species. The scales demonstrated strong construct validity, with factor structures consistent with theoretical expectations and evidence of convergent and discriminant validity. Concurrent validity was supported through associations with related attitudes and behavioral intentions. These instruments offer researchers a robust, theory‐driven framework for examining human–wildlife interactions that facilitates standardized comparisons across species and contexts. For practitioners, the psychometric scales provide a practical means to assess public readiness for coexistence, monitor attitudinal change over time, and design interventions tailored to specific belief structures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Ten years on: Are raw material criticality assessments making more sense? - Baptiste Andrieu; Benjamin Adams; Mehrnoosh Heydari; Philip Mitchell; Luke Cullen; Alexey Noskov; Julian M. Allwood; André Cabrera Serrenho; Jonathan Cullen (Resources, Conservation and Recycling, 2026)

Water Exchange Characteristics of Tidally Influenced Hydrilla Invasion Sites in the Lower Connecticut River - Andrew W. Howell; Benjamin P. Sperry; Jens P. Beets; Michael W. Durham; Jonathan S. Glueckert; Amber E. Riner (Estuaries and Coasts, 2026)
The Lower Connecticut River (CR) is an ecologically and recreationally significant ecosystem within New England, but the river has become increasingly vulnerable to the intrusion of aquatic invasive species (AIS) like hydrilla ( Hydrilla verticillata ). The hydrilla population recently discovered in the Lower CR is genetically unlike former hydrilla clades present in the United States. The specific biological and management components of this unique clade-C hydrilla in comparison to its cohorts remains largely undetermined and the nature of management action to combat the submersed plant within the tidally influenced lotic system further complicates waterway resilience efforts due to high-water exchange. Because of the inherent environmental challenges attributed to lotic environs, the use of aquatic herbicides remains the primary management tool for selective and effective hydrilla control. However, knowledge of the site-specific water exchange processes at infested sites coupled with subspecies- and herbicide-specific concentration-exposure time (CET) requirements are essential for successful plant management. The primary goal of the present studies was to quantify bulk water exchange rates at five representative hydrilla infestation sites within the Lower CR using Rhodamine WT dye (RWT) to mimic prospective herbicide application operations. Dye monitoring indicated distinct variability among study site water exchange rates, with RWT half-lives ranging from 0.35 to 72.36 h following application. Future management efforts deploying herbicide should consider these methods and findings when selecting appropriate herbicide active ingredients and use rates to achieve hydrilla control. While the present water exchange findings offer initial guidance, comparable dye studies will be necessary as management programs target additional hydrilla invasion areas within the river.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Stochastic modelling of burden of livestock diseases on domestic ruminants in Ethiopia - Wudu T. Jemberu; Gemma Chaters; Theodore J.D. Knight-Jones; William Gilbert; Stephen Kwok; Mieghan Bruce; Benjamin Huntington; Jonathan Rushton (Preventive Veterinary Medicine, 2026)

Stable nutritional provisioning emerges from interactions between leafcutter ants and their mutualistic fungal cultivar - Aoife O'Brien; Anke J. Posma; Olivia-Sofie Basse Schougaard; Marta Contreras-Serrano; Caio A. Leal-Dutra; Benjamin H. Conlon; Jonathan Z. Shik (Animal Behaviour, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Stone artefacts on submerged land surfaces: A response to Larcombe et al. - Michael O'Leary; Jonathan Benjamin; Jo McDonald; Sean Ulm; Geoff Bailey (Geomorphology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Oyster drills Stramonita haemastoma use mechanical cues to make foraging decisions - Jonathan D. Mai; Benjamin A. Belgrad; Jessica Lunt; Randi Cannon; Jessica Hilliker; Delbert L. Smee (Journal of Experimental Marine Biology and Ecology, 2025)

Academic Achievement of Children and Adolescents with Neurofibromatosis Type 1: A Systematic Review and Meta-Analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Xian Wu; Heather L. Thompson; Julia Moreira; Lauren Morey; Benjamin Felipe Mujica; Yang Hou (Neuropsychology Review, 2025)

Evaluating soil nutrient status and crop production under traditional Jhum and sustainable farming systems in Mizoram, North East India - Benjamin Lalengliana Sailo; Jonathan Lalrinawma; Vanlalsawma; H. Lalrinngheta; R. Zonunsanga; Laldinpuia; Lallawmzuali; Lalhmingmuana (Environmental Monitoring and Assessment, 2025)

Indoor air treatment of formaldehyde by N-enriched activated carbon beads with or without CuO/Cu supported nanoparticles - Laurence Reinert; Michel Ondarts; Laurent Duclaux; Fabrice Guy; Peter Moonen; Emilie Planes; Jonathan Outin; Benjamin Golly; Evelyne Gonze; Yasushi Soneda (Process Safety and Environmental Protection, 2025)

A Safe Operating Space for Salmon Watersheds Under Rapid Climate Change - Jonathan W. Moore; Marta E. Ulaski; Kyle L. Wilson; Tara G. Martin; Spencer Dakin Kuiper; Stephanie J. Peacock; Douglas C. Braun; Sean M. Naman; Kara J. Pitman; Andrea J. Reid; Jordan S. Rosenfeld; Nigel C. Sainsbury; et al. (Fish and Fisheries, 2025)
Climate change and local pressures are eroding the health and performance of many watersheds and their freshwater ecosystems, pushing these complex social‐ecological systems to the boundaries of their safe operating space. Here, we offer a synthetic perspective on the downscaled application of the safe operating space concept to inform the stewardship of watersheds in this time of rapid climate change, with particular focus on watersheds that support coldwater migratory fishes such as Pacific salmon. First, we review the safe operating space concept as it applies to salmon watersheds as social‐ecological systems. Salmon watersheds, and the benefits they provide for diverse peoples, are under enormous cumulative pressure from climate change as well as local activities such as forestry, urbanisation, mining and agriculture. We identify four general syndromes of dual local and climate pressures. For example, local pressures, such as the removal of riparian vegetation that shades streams, can exacerbate climate warming of water temperatures. Furthermore, extractive industries can damage or destroy future habitats and thus erode adaptive capacity. As an illustrative example of how the safe operating space concept can be operationalised, we assess alternative plausible watershed futures of land use and climate change scenarios and salmon performance. Collectively, this work showcases tangible options for local management to help give salmon watersheds the time and space to cope with climate change. More broadly, while there is a global need to address climate change, local watershed management is a key component of pathways towards freshwater sustainability and their services for humanity.

Fishers' Local Ecological Knowledge Reveals Complex Food Web Dynamics With Rapidly Warming Waters - Loren McClenachan; Benjamin Neal; Marissa McMahan; Ellie Batchelder; Neida Villanueva‐Galarza; Jonathan Grabowski (Fish and Fisheries, 2025)
Local ecological knowledge (LEK) can provide insight into ecosystem change, particularly in dynamic ecological conditions, such as those driven by climate change. In New England lobster fisheries, warming waters have the potential to disrupt food webs, as range‐shifting species introduce novel ecological interactions. Here we use interviews with lobster fishers in Maine and Massachusetts to understand lobster fishers' LEK of dynamic food webs, taking a mental modelling approach to construct LEK food web models under rapidly warming waters. We find that fishers are observing a remarkable range of ecological interactions across habitats, collectively reporting knowledge of > 35 species that interact trophically with lobster across larval, juvenile, and adult life stages, ranging from terrestrial species like mink ( Neovison vison ) to deep sea species like redfish ( Sebastes fasciatus ). Our LEK food webs demonstrate perceptions of warming water altering species' abundances and interactions, with an overall negative impact on lobster fisheries. Fishers also report knowledge of complex interactions, including predation, competition, and habitat loss mediated by warming waters and changing species' abundances. Finally, we identify and categorise three main pathways that contribute to fishers' LEK, including observation, word of mouth, and inference. Our findings demonstrate that active fishers have complex understandings of food web interactions in dynamic ecosystems that are changing rapidly. With management unable to keep pace with climate‐driven change, fishers' LEK is an invaluable source of knowledge, whose use could improve the ability to understand the diverse impacts of warming waters on coastal ecosystems.

Taking advantage of open data in coastal science and conservation - Nicholas M. Hoad; Jonathan S. Lefcheck; Nikolaos Alexandridis; Benjamin L.H. Jones; Johan S. Eklöf; Lina Mtwana Nordlund (Science of The Total Environment, 2025)

Evaluation of a novel approach to partitioning respiration and photosynthesis using eddy covariance, wavelets and conditional sampling - Pedro Henrique H. Coimbra; Benjamin Loubet; Olivier Laurent; Matthias Mauder; Bernard Heinesch; Jonathan Bitton; Nicolas Delpierre; Daniel Berveiller; Jérémie Depuydt; Pauline Buysse (Agricultural and Forest Meteorology, 2025)

Molecular Mechanisms Underlying Response to Influenza in Grey Seals ( Halichoerus grypus ), a Potential Wild Reservoir - Christina M. McCosker; Ebru Unal; Alayna Gigliotti; Wendy B. Puryear; Jonathan A. Runstadler; Kimberly T. Murray; Benjamin L. King; Kristina M. Cammen (Molecular Ecology, 2025)
RNA viruses are infamous for their ability to cross species barriers, posing threats to global health and security. Influenza A virus (IAV) is naturally found in avian hosts but periodically spills over into marine wildlife. IAV outbreaks occur in the Northwest Atlantic, but grey seals ( Halichoerus grypus ) appear to be less susceptible to IAV compared to other species. The subclinical nature of IAV infection in addition to life history factors suggest grey seals are a potential wild reservoir host for IAV. We investigated differential gene expression among grey seals naturally exposed to IAV to elucidate genetic mechanisms involved in grey seal disease resistance. RNA sequencing was conducted on blood samples ( N = 31) collected from grey seal pups in Massachusetts, US between 2014 and 2019. Samples were grouped for analysis based on presence/absence of viral RNA and antibodies. In the presence of IAV RNA, we observed widespread down‐regulation of genes, including immune genes, potentially as a result of IAV‐induced host shutoff. Immune down‐regulation occurred in acute stage of IAV infection (+ viral RNA, − antibodies), followed by up‐regulation of protein production in peak stage (+ viral RNA, + antibodies), possibly as a result of increased viral replication. Evidence of an activated immune response was observed in late stage of infection (− viral RNA, + antibodies) with up‐regulated adaptive immunity genes. We hypothesize that the combination of down‐ and up‐regulated immune gene expression may prevent overstimulation of the immune response, acting as an adaptation in grey seals to resist IAV‐associated mortality.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

Global Change Affects Large Herbivore Forage Biomass Through Gradual Successional Shifts and Abrupt Disturbances - Jonathan J. Farr; Sarah M. Straughan; Benjamin Larue; Tara K. Meyer; Jesse Whittington; Dillon J. Watt; Anne Hubbs; Evelyn H. Merrill; Mark Hebblewhite (Global Change Biology, 2025)
Forage availability is a key factor regulating large herbivore populations. Global changes in land use and climate may affect the spatiotemporal distribution of forage across the ranges of large herbivores, especially in mountain ecosystems. We test two synergistic hypotheses for how landscape and climate changes from 2001 to 2023 have affected forb and graminoid biomass at the peak of the growing season within and across ecoregions of the eastern slopes of the Rocky Mountains in Alberta, Canada. The successional change hypothesis posits that the encroachment of woody vegetation into previously herbaceous communities has reduced forage biomass. The disturbance hypothesis proposes that abrupt community shifts caused by fire and timber harvesting have increased forage biomass. Using remote sensing, we quantify temporal changes in land cover and disturbances, NDVI greenness and phenology indices, and spring climate. We then used in situ vegetation data to parameterize generalized linear and gradient boosted regression tree models of forb and graminoid biomass to predict annual peak forb and graminoid biomass. Herbaceous land cover declined while shrub and forest area increased, and the percent of annual biomass within herbaceous areas declined from woody encroachment. Disturbance effects varied, with rising forage biomass in conjunction with increased area of logged forests in the foothills ecoregion, while burned areas declined and had a reduced contribution to the percent of annual biomass. Additionally, spring became warmer across the study area and ended earlier in the alpine, suggesting the effects of long‐term climatic shifts may be strongest at higher ecoregions. Disturbance frequency, succession, and climate together shaped forage biomass in space and time. Increased prescribed fire and other ecological restoration actions may be needed to ensure that shifts in forage biomass do not threaten large herbivore persistence in the face of global change.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Multi-energy systems fast optimization: A new formulation in linear programming for temperatures and magnitudes of thermal power flows in heating systems - Jonathan Hachez; Arnaud Latiers; Benjamin Berger; Svend Bram (Energy and Buildings, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Nutrient limitation and seasonality associated with phytoplankton communities and cyanotoxin production in a large, hypereutrophic lake - Gabriella M. Lawson; Jakob L. Young; Zachary T. Aanderud; Erin F. Jones; Samuel Bratsman; Jonathan Daniels; Madeleine P. Malmfeldt; Michelle A. Baker; Benjamin W. Abbott; Scott Daly; Hans W. Paerl; Greg Carling; et al. (Harmful Algae, 2025)

Identification of Spectral Fingerprints in Different Batches of Antimalarial Herbal Drugs Using Laser-Induced Autofluorescence and Chemometric Techniques - Jerry Opoku-Ansah; Rabbi Boateng; Charles Lloyd Yeboah Amuah; Peter Osei-Wusu Adueming; Justice Allotey Pappoe; Jonathan Ntow; Kwesi Quagraine; Shemmira Yunus; Benjamin Anderson; Moses Jojo Eghan (Journal of Fluorescence, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Incorporating Singaporean habits and practices for cosmetics and personal care products into a global consumer aggregate exposure model - Siti Amelia Juraimi; Cesar Scrochi; Jonathan Lok; Anne Marie Api; Benjamin P.C. Smith (Regulatory Toxicology and Pharmacology, 2025)

Minimising the relative regret of future forest landscape compositions: The role of close-to-nature stand types - Thomas Knoke; Peter Biber; Tobias Schula; Jonathan Fibich; Benjamin Gang (Forest Policy and Economics, 2025)

Clinical Validation of Non-invasive Simulation-Based Determination of Vascular Impedance, Wave Intensity, and Hydraulic Work in Patients Undergoing Transcatheter Aortic Valve Replacement - Jonathan Y. Brown; Gabriela Veiga Fernandez; Jose M. De La Torre Hernández; Michael Murphy; Benjamin S. Wessler; Elazer R. Edelman (Annals of Biomedical Engineering, 2025)
Purpose The impact of Aortic Stenosis (AS) on the left ventricle (LV) extends beyond the influence of the pressure drop across the stenotic valve, but also includes the additional serial afterload imposed by the vascular system. Aortic input impedance is the gold standard for comprehensively studying the contribution of the vascular system to total myocardial afterload, but in the past measurement has been challenging arising from the need for invasive catheterization or specialized equipment to precisely record time-resolved blood pressure and flow signals. The goal of this work was to develop and validate a novel simulation-based method for determining aortic input impedance using only clinically available echocardiographic data and a simple blood pressure measurement. Methods A simulation-based method to determine vascular impedance was developed using echocardiographic data and a brachial blood pressure measurement. Simulation-based impedance was compared to impedance calculated from echocardiographic flow data and pressure data from a non-invasive central pressure measurement device. Results In validation analysis comparing patient-specific simulation-based vascular impedance to non-invasively measured impedance, correlation between methods across a range of vascular parameters varied between R 2 = 0.40 and 0.99. A tendency was seen toward underestimation of pressure waveforms in point-by-point comparison of measured and simulated waveforms with an overall mean difference of 4.01 mmHg. Conclusions Requiring only non-invasive clinical data that are widely available, simulation-based vascular impedance has the potential to allow for easier, more widespread, and larger-scale investigation of the effect of vascular impedance on total LV afterload.

Economic assessment of animal disease burden in Senegalese small ruminants - Anne Meyer; Bakary Ndiaye; Andrew Larkins; Gemma Chaters; William Gilbert; Benjamin Huntington; Guy Ilboudo; Michel Dione; Wudu Temesgen Jemberu; Mame Nahé Diouf; Assane Gueye Fall; Mathioro Fall; et al. (Preventive Veterinary Medicine, 2025)

After the n10: late oVEMP peaks in patients with unilateral vestibular loss and healthy volunteers - Alyssa C. Dyball; Xiao Ping Wu; Belinda Y. C Kwok; Chao Wang; Benjamin Nham; Jacob M. Pogson; Jonathan H. K. Kong; Rachael L. Taylor; Konrad P. Weber; Miriam S. Welgampola; Sally M. Rosengren (Experimental Brain Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Prioritization, resource allocation and utilization of decision support tools in animal health: Results of qualitative interviews with experts - Kebede Amenu; Chris Daborn; Benjamin Huntington; Theodore Knight-Jones; Jonathan Rushton; Delia Grace (Preventive Veterinary Medicine, 2024)

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Seasonality Structures Avian Functional Diversity and Niche Packing Across North America - Spencer R. Keyser; Jonathan N. Pauli; Daniel Fink; Volker C. Radeloff; Alex L. Pigot; Benjamin Zuckerberg (Ecology Letters, 2024)
Assemblages in seasonal ecosystems undergo striking changes in species composition and diversity across the annual cycle. Despite a long‐standing recognition that seasonality structures biogeographic gradients in taxonomic diversity (e.g., species richness), our understanding of how seasonality structures other aspects of biodiversity (e.g., functional diversity) has lagged. Integrating seasonal species distributions with comprehensive data on key morphological traits for bird assemblages across North America, we find that seasonal turnover in functional diversity increases with the magnitude and predictability of seasonality. Furthermore, seasonal increases in bird species richness led to a denser packing of functional trait space, but functional expansion was important, especially in regions with higher seasonality. Our results suggest that the magnitude and predictability of seasonality and total productivity can explain the geography of changes in functional diversity with broader implications for understanding species redistribution, community assembly and ecosystem functioning.

Age-induced changes in skeletal muscle mitochondrial DNA synthesis, quantity, and quality in genetically unique rats - Robert V. Musci; Jordan D. Fuqua; Frederick F. Peelor; Hoang Van Michelle Nguyen; Arlan Richardson; Solbie Choi; Benjamin F. Miller; Jonathan Wanagat (GeroScience, 2024)
Mitochondrial genomic integrity is a key element of physiological processes and health. Changes in the half-life of the mitochondrial genome are implicated in the generation and accumulation of age-induced mitochondrial DNA (mtDNA) mutations, which are implicated in skeletal muscle aging and sarcopenia. There are conflicting data on the half-life of mtDNA, and there is limited information on how aging affects half-life in skeletal muscle. We hypothesized that skeletal muscle mtDNA synthesis rates would decrease with age in both female and male rats concomitant with changes in mtDNA integrity reflected in mtDNA copy number and mutation frequency. We measured mitochondrial genome half-life using stable isotope labeling over a period of 14 days and assessed mtDNA copy number and deletion mutation frequency using digital PCR in the quadriceps muscle of 9-month-old and 26-month-old male and female OKC-HET rats. We found a significant age-related increase in mtDNA half-life, from 132 days at 9 months to 216 days at 26 months of age in OKC-HET quadriceps. Concomitant with the increase in mtDNA half-life, we found an age-related increase in mtDNA deletion mutation frequency in both male and female rats. Notably, 26-month-old female rats had a lower mutation frequency than male rats, and there were no changes in mtDNA copy number with sex, age, or mitochondrial genotype. These data reveal several key findings: (1) mtDNA turnover in rat skeletal muscle decreases with age, (2) mtDNA half-lives in skeletal muscle are approximately an order of magnitude longer than what is reported for other tissues, and (3) muscle mtDNA turnover differs significantly from the turnover of other mitochondrial macromolecules including components of the mitochondrial nucleoid. These findings provide insight into the factors driving age-induced mtDNA mutation accumulation, which contribute to losses of mitochondrial genomic integrity and may play a role in skeletal muscle dysfunction.

Change in growth and prey utilization for a native salmonid following invasion by an omnivorous minnow in an oligotrophic reservoir - Rachelle C. Johnson; Tessa J. Code; Karl D. Stenberg; Jonathan H. Mclean; Benjamin L. Jensen; Marshal S. Hoy; David A. Beauchamp (Hydrobiologia, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Variability in flood frequency in sub-Saharan Africa: The role of large-scale climate modes of variability and their future impacts - Job Ekolu; Bastien Dieppois; Yves Tramblay; Gabriele Villarini; Louise J. Slater; Gil Mahé; Jean-Emmanuel Paturel; Jonathan M. Eden; Simon Moulds; Moussa Sidibe; Pierre Camberlin; Benjamin Pohl; et al. (Journal of Hydrology, 2024)

A framework for physically consistent storylines of UK future mean sea level rise - Matthew D. Palmer; Benjamin J. Harrison; Jonathan M. Gregory; Helene T. Hewitt; Jason A. Lowe; Jennifer H. Weeks (Climatic Change, 2024)
We present a framework for developing storylines of UK sea level rise to aid risk communication and coastal adaptation planning. Our approach builds on the UK national climate projections (UKCP18) and maintains the same physically consistent methods that preserve component correlations and traceability between global mean sea level (GMSL) and local relative sea level (RSL). Five example storylines are presented that represent singular trajectories of future sea level rise drawn from the underlying large Monte Carlo simulations. The first three storylines span the total range of the Intergovernmental Panel on Climate Change (IPCC) Sixth Assessment Report (AR6) likely range GMSL projections across the SSP1-2.6 and SSP5-8.5 scenarios. The final two storylines are based upon recent high-end storylines of GMSL presented in AR6 and the recent literature. Our results suggest that even the most optimistic sea level rise outcomes for the UK will require adaptation of up to 1 m of sea level rise for large sections of coastline by 2300. For the storyline most consistent with current international greenhouse gas emissions pledges and a moderate sea level rise response, UK capital cities will experience between about 1 and 2 m of sea level rise by 2300, with continued rise beyond 2300. The storyline based on the upper end of the AR6 likely range sea level projections yields much larger values for UK capital cities that range between about 3 and 4 m at 2300. The two high-end scenarios, which are based on a recent study that showed accelerated sea level rise associated with ice sheet instability feedbacks, lead to sea level rise for UK capital cities at 2300 that range between about 8 m and 17 m. These magnitudes of rise would pose enormous challenges for UK coastal communities and are likely to be beyond the limits of adaptation at some locations.

Mining exploration infrastructure affects biophysical habitat characteristics and ground-dwelling arthropod communities - Kristen Fernandes; Sophia Clark-Ioannou; Benjamin J. Saunders; Jonathan Majer; Philip W. Bateman; Michael Bunce; Paul Nevill (Biodiversity and Conservation, 2024)
Monitoring of environmental impacts of mining activities typically focuses on the main operation footprint, neglecting exploration infrastructure like tracks, roads, and drill pads. These areas are cleared of native vegetation and impacts on the surrounding environment can be both cumulative and enigmatic. Here, we study the impacts of mining exploration infrastructure on habitat characteristics and ground-dwelling arthropod communities in the Midwest region of Western Australia. The study was conducted at three mine sites, each with three infrastructure types: maintained tracks, unmaintained tracks, and drill pads along transects extending 100 m away from the disturbance into remnant vegetation. Habitat characteristics were measured, and arthropods collected from pitfall traps along these transects and identified using COI metabarcoding. The overall arthropod community and two indicator groups, ants (Formicidae) and springtails (Collembola) - were used to measure arthropod responses to changes in response to habitat disturbance. Whilst changes in habitat were only visible to 10 m from the disturbance, impacts on arthropod communities could be detected up to 100 m into the remnant vegetation, and these responses were more complex. In general, we found similar patterns expressed in the compositional changes for arthropods overall and between our chosen indicator groups, but they were not the same across all sites and infrastructure types. Our results demonstrate the utility of bulk arthropod metabarcoding and different arthropod indicator groups for documenting the effects of fine-scale habitat destruction, degradation, or disturbance. They also highlight the need to monitor the negative impacts of mineral exploration on the environment.

Twenty-first century marine climate projections for the NW European shelf seas based on a perturbed parameter ensemble - Jonathan Tinker; Matthew D. Palmer; Benjamin J. Harrison; Enda O'Dea; David M. H. Sexton; Kuniko Yamazaki; John W. Rostron (Ocean Science, 2024)
The northwest European shelf (NWS) seas are environmentally and economically important, and an understanding of how their climate may change helps with their management. However, as the NWS seas are poorly represented in global climate models, a common approach is to dynamically downscale with an appropriate shelf sea model. We develop a set of physical marine climate projections for the NWS. We dynamically downscale 12 members of the HadGEM3-GC3.05 perturbed parameter ensemble (approximately 70 km horizontal resolution over Europe), developed for UKCP18, using the shelf sea model NEMO CO9 (7 km horizontal resolution). These are run under the RCP8.5 high-greenhouse-gas-emission scenario as continuous simulations over the period 1990–2098. We evaluate the simulations against observations in terms of tides, sea surface temperature (SST), surface and near-bed temperature and salinity, and sea surface height. These simulations represent the state of the art for NWS marine projections. We project an SST rise of 3.11 °C (± 2σ = 0.98 °C) and a sea surface salinity (SSS) freshening of −1.01 (± 2σ = 0.93; on the (unitless) practical salinity scale) for 2079–2098 relative to 2000–2019, averaged over the NWS (approximately bounded by the 200 m isobar and excluding the Norwegian Trench, the Skagerrak and Kattegat), a substantial seasonal stratification increase (23 d over the NWS seas), and a general weakening of the NWS residual circulation. While the patterns of NWS changes are similar to our previous projections, there is a greater warming and freshening that could reflect the change from the A1B emissions scenario to the RCP8.5 concentrations pathway or the higher climate sensitivity exhibited by HadGEM3-GC3.05. Off the shelf, south of Iceland, there is limited warming, consistent with a reduction in the Atlantic Meridional Overturning Circulation and associated northward heat transport. These projections have been publicly released, along with a consistent 200-year present-day control simulation, to provide an evidence base for climate change assessments and to facilitate climate impact studies. For example, we illustrate how the two products can be used to estimate climate trends, unforced variability and the time of emergence (ToE) of the climate signals. We calculate the average NWS SST ToE to be 2034 (with an 8-year range) and 2046 (with a 33-year range) for SSS. We also discuss how these projections can be used to describe NWS conditions under 2 and 4 °C global mean warming (compared with 1850–1900), as a policy-relevant exemplar use case.

Repurposing the KCa3.1 Blocker Senicapoc for Ischemic Stroke - Ruth D. Lee; Yi-Je Chen; Hai M. Nguyen; Latika Singh; Connor J. Dietrich; Benjamin R. Pyles; Yanjun Cui; Jonathan R. Weinstein; Heike Wulff (Translational Stroke Research, 2024)
Senicapoc, a small molecule inhibitor of the calcium-activated potassium channel KCa3.1, was safe and well-tolerated in clinical trials for sickle cell anemia. We previously reported proof-of-concept data suggesting that both pharmacological inhibition and genetic deletion of KCa3.1 reduces infarction and improves neurologic recovery in rodents by attenuating neuroinflammation. Here we evaluated the potential of repurposing senicapoc for ischemic stroke. In cultured microglia, senicapoc inhibited KCa3.1 currents with an IC 50 of 7 nM, reduced Ca 2+ signaling induced by the purinergic agonist ATP, suppressed expression of pro-inflammatory cytokines and enzymes (iNOS and COX-2), and prevented induction of the inflammasome component NLRP3 . When transient middle cerebral artery occlusion (tMCAO, 60 min) was induced in male C57BL/6 J mice, twice daily administration of senicapoc at 10 and 40 mg/kg starting 12 h after reperfusion dose-dependently reduced infarct area determined by T2-weighted magnetic resonance imaging (MRI) and improved neurological deficit on day 8. Ultra-high-performance liquid chromatography/mass spectrometry analysis of total and free brain concentrations demonstrated sufficient KCa3.1 target engagement. Senicapoc treatment significantly reduced microglia/macrophage and T cell infiltration and activation and attenuated neuronal death. A different treatment paradigm with senicapoc started at 3 h and MRI on day 3 and day 8 revealed that senicapoc reduces secondary infarct growth and suppresses expression of inflammation markers, including T cell cytokines in the brain. Lastly, we demonstrated that senicapoc does not impair the proteolytic activity of tissue plasminogen activator (tPA) in vitro. We suggest that senicapoc could be repurposed as an adjunctive immunocytoprotective agent for combination with reperfusion therapy for ischemic stroke.

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Current and potential use of animal disease data by stakeholders in the global south and north - Delia Grace; Kebede Amenu; Chris J. Daborn; Theodore Knight-Jones; Benjamin Huntington; Stephen Young; Jane Poole; Jonathan Rushton (Preventive Veterinary Medicine, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

DeepSTARia: enabling autonomous, targeted observations of ocean life in the deep sea - Kevin Barnard; Joost Daniels; Paul L. D. Roberts; Eric C. Orenstein; Ivan Masmitja; Jonathan Takahashi; Benjamin Woodward; Kakani Katija (Frontiers in Marine Science, 2024)
The ocean remains one of the least explored places on our planet, containing myriad life that are either unknown to science or poorly understood. Given the technological challenges and limited resources available for exploring this vast space, more targeted approaches are required to scale spatiotemporal observations and monitoring of ocean life. The promise of autonomous underwater vehicles to fulfill these needs has largely been hindered by their inability to adapt their behavior in real-time based on what they are observing. To overcome this challenge, we developed Deep Search and Tracking Autonomously with Robotics ( DeepSTARia ), a class of tracking-by-detection algorithms that integrate machine learning models with imaging and vehicle controllers to enable autonomous underwater vehicles to make targeted visual observations of ocean life. We show that these algorithms enable new, scalable sampling strategies that build on traditional operational modes, permitting more detailed (e.g., sharper imagery, temporal resolution) autonomous observations of underwater concepts without supervision and robust long-duration object tracking to observe animal behavior. This integration is critical to scale undersea exploration and represents a significant advance toward more intelligent approaches to understanding the ocean and its inhabitants.

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Spatio-temporal patterns of rangeland forage nutritive value and grazer selection with patch-burning in the US northern Great Plains - Jonathan W. Spiess; Devan Allen McGranahan; Marisol T. Berti; Caley K. Gasch; Torre Hovick; Benjamin Geaumont (Journal of Environmental Management, 2024)

A novel paradigm for observational learning in rats - Ida V. Rautio; Ella Holt Holmberg; Devika Kurup; Benjamin A. Dunn; Jonathan R. Whitlock (Cognitive Neurodynamics, 2024)
The ability to learn by observing the behavior of others is energy efficient and brings high survival value, making it an important learning tool that has been documented in a myriad of species in the animal kingdom. In the laboratory, rodents have proven useful models for studying different forms of observational learning, however, the most robust learning paradigms typically rely on aversive stimuli, like foot shocks, to drive the social acquisition of fear. Non-fear-based tasks have also been used but they rarely succeed in having observer animals perform a new behavior de novo . Consequently, little known regarding the cellular mechanisms supporting non-aversive types of learning, such as visuomotor skill acquisition. To address this we developed a reward-based observational learning paradigm in adult rats, in which observer animals learn to tap lit spheres in a specific sequence by watching skilled demonstrators, with successful trials leading to rewarding intracranial stimulation in both observers and performers. Following three days of observation and a 24-hour delay, observer animals outperformed control animals on several metrics of task performance and efficiency, with a subset of observers demonstrating correct performance immediately when tested. This paradigm thus introduces a novel tool to investigate the neural circuits supporting observational learning and memory for visuomotor behavior, a phenomenon about which little is understood, particularly in rodents.

Interplay of management and environmental drivers shifts size structure of reef fish communities - Steven W. J. Canty; A. Justin Nowakowski; Courtney E. Cox; Abel Valdivia; Daniel M. Holstein; Benjamin Limer; Jonathan S. Lefcheck; Nicole Craig; Ian Drysdale; Ana Giro; Mélina Soto; Melanie McField (Global Change Biology, 2024)
Countries are expanding marine protected area (MPA) networks to mitigate fisheries declines and support marine biodiversity. However, MPA impact evaluations typically assess total fish biomass. Here, we examine how fish biomass disaggregated by adult and juvenile life stages responds to environmental drivers, including sea surface temperature (SST) anomalies and human footprint, and multiple management types at 139 reef sites in the Mesoamerican Reef (MAR) region. We found that total fish biomass generally appears stable across the region from 2006 to 2018, with limited rebuilding of fish stocks in MPAs. However, the metric of total fish biomass masked changes in fish community structure, with lower adult than juvenile fish biomass at northern sites, and adult:juvenile ratios closer to 1:1 at southern sites. These shifts were associated with different responses of juvenile and adult fish to environmental drivers and management. Juvenile fish biomass increased at sites with high larval connectivity and coral cover, whereas adult fish biomass decreased at sites with greater human footprint and SST anomalies. Adult fish biomass decreased primarily in Honduran general use zones, which suggests insufficient protection for adult fish in the southern MAR. There was a north–south gradient in management and environmental drivers, with lower coverage of fully protected areas and higher SST anomalies and coastal development in the south that together may undermine the maintenance of adult fish biomass in the southern MAR. Accounting for the interplay between environmental drivers and management in the design of MPAs is critical for increasing fish biomass across life history stages.

Intensification of harmful cyanobacterial blooms in a eutrophic, temperate lake caused by nitrogen, temperature, and CO2 - Benjamin J. Kramer; Kendra Turk-Kubo; Jonathan P. Zehr; Christopher J. Gobler (Science of The Total Environment, 2024)

Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; K. Marie McIntyre; Philip Rasmussen; William Gilbert; Gemma Chaters; Kassy Raymond; Wudu T. Jemberu; Andrew Larkins; Grace T. Patterson; Stephen Kwok; Alexander James Kappes; Dianne Mayberry; et al. (Research in Veterinary Science, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Recommendations for Method Development and Validation of qPCR and dPCR Assays in Support of Cell and Gene Therapy Drug Development - Amanda Hays; Mark Wissel; Kelly Colletti; Russell Soon; Mitra Azadeh; Justin Smith; Rajitha Doddareddy; Melanie Chalfant; Wendy Adamowicz; Swarna Suba Ramaswamy; Sanjay L. Dholakiya; Sebastian Guelman; et al. (The AAPS Journal, 2024)
The emerging use of qPCR and dPCR in regulated bioanalysis and absence of regulatory guidance on assay validations for these platforms has resulted in discussions on lack of harmonization on assay design and appropriate acceptance criteria for these assays. Both qPCR and dPCR are extensively used to answer bioanalytical questions for novel modalities such as cell and gene therapies. Following cross-industry conversations on the lack of information and guidelines for these assays, an American Association of Pharmaceutical Scientists working group was formed to address these gaps by bringing together 37 industry experts from 24 organizations to discuss best practices to gain a better understanding in the industry and facilitate filings to health authorities. Herein, this team provides considerations on assay design, development, and validation testing for PCR assays that are used in cell and gene therapies including (1) biodistribution; (2) transgene expression; (3) viral shedding; (4) and persistence or cellular kinetics of cell therapies. Graphical Abstract

Size matters: Microherbivores make a big impact in coral aquaculture - Rachel C. Neil; Jonathan A. Barton; Winona Dougan; Symon Dworjanyn; Andrew Heyward; Benjamin Mos; David G. Bourne; Craig Humphrey (Aquaculture, 2024)

Analytical solutions to evaluate the geothermal energy generation potential from sedimentary-basin reservoirs - Daniel T. Birdsell; Benjamin M. Adams; Paromita Deb; Jonathan D. Ogland-Hand; Jeffrey M. Bielicki; Mark R. Fleming; Martin O. Saar (Geothermics, 2024)

Approximating the global economic (market) value of farmed animals - Peggy Schrobback; Gabriel Dennis; Yin Li; Dianne Mayberry; Alexandra Shaw; Theodore Knight-Jones; Thomas Lloyd Marsh; Dustin L. Pendell; Paul R. Torgerson; William Gilbert; Benjamin Huntington; Kassy Raymond; et al. (Global Food Security, 2023)

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

AgAnimalGenomes: browsers for viewing and manually annotating farm animal genomes - Deborah A. Triant; Amy T. Walsh; Gabrielle A. Hartley; Bruna Petry; Morgan R. Stegemiller; Benjamin M. Nelson; Makenna M. McKendrick; Emily P. Fuller; Noelle E. Cockett; James E. Koltes; Stephanie D. McKay; Jonathan A. Green; et al. (Mammalian Genome, 2023)
Current genome sequencing technologies have made it possible to generate highly contiguous genome assemblies for non-model animal species. Despite advances in genome assembly methods, there is still room for improvement in the delineation of specific gene features in the genomes. Here we present genome visualization and annotation tools to support seven livestock species (bovine, chicken, goat, horse, pig, sheep, and water buffalo), available in a new resource called AgAnimalGenomes. In addition to supporting the manual refinement of gene models, these browsers provide visualization tracks for hundreds of RNAseq experiments, as well as data generated by the Functional Annotation of Animal Genomes (FAANG) Consortium. For species with predicted gene sets from both Ensembl and RefSeq, the browsers provide special tracks showing the thousands of protein-coding genes that disagree across the two gene sources, serving as a valuable resource to alert researchers to gene model issues that may affect data interpretation. We describe the data and search methods available in the new genome browsers and how to use the provided tools to edit and create new gene models.

Stone artefacts on the seabed at a submerged freshwater spring confirm a drowned cultural landscape in Murujuga, Western Australia - Jonathan Benjamin; Michael O'Leary; John McCarthy; Wendy Reynen; Chelsea Wiseman; Jerem Leach; Simon Bobeldyk; Justine Buchler; Philippe Kermeen; Michelle Langley; Adam Black; Hiro Yoshida; et al. (Quaternary Science Reviews, 2023)

Older forests function as energetic and demographic refugia for a climate-sensitive species - Kate A. McGinn; Benjamin Zuckerberg; Jonathan N. Pauli; Ceeanna J. Zulla; William J. Berigan; Zachary A. Wilkinson; Josh M. Barry; John J. Keane; R. J. Gutiérrez; M. Zachariah Peery (Oecologia, 2023)

Anchor geotechnics for floating offshore wind: Current technologies and future innovations - Benjamin Cerfontaine; David White; Katherine Kwa; Susan Gourvenec; Jonathan Knappett; Michael Brown (Ocean Engineering, 2023)

The demographics of energy and mobility poverty: Assessing equity and justice in Ireland, Mexico, and the United Arab Emirates - Jonathan Furszyfer Del Rio; Dylan D. Furszyfer Del Rio; Benjamin K. Sovacool; Steve Griffiths (Global Environmental Change, 2023)

Phenotypic variation in the molt characteristics of a seasonal coat color-changing species reveals limited resilience to climate change - Taylor R. Peltier; Shotaro Shiratsuru; Benjamin Zuckerberg; Mark Romanski; Lynette Potvin; Andrew Edwards; Jonathan H. Gilbert; Tanya R. Aldred; Ann Dassow; Jonathan N. Pauli (Oecologia, 2023)

A phenology of fear: Investigating scale and seasonality in predator–prey games between wolves and white‐tailed deer - John D. J. Clare; Benjamin Zuckerberg; Nanfeng Liu; Jennifer L. Stenglein; Timothy R. Van Deelen; Jonathan N. Pauli; Philip A. Townsend (Ecology, 2023)
Predators and prey engage in games where each player must counter the moves of the other, and these games include multiple phases operating at different spatiotemporal scales. Recent work has highlighted potential issues related to scale‐sensitive inferences in predator–prey interactions, and there is growing appreciation that these may exhibit pronounced but predictable dynamics. Motivated by previous assertions about effects arising from foraging games between white‐tailed deer and canid predators (coyotes and wolves), we used a large and year‐round network of trail cameras to characterize deer and predator foraging games, with a particular focus on clarifying its temporal scale and seasonal variation. Linear features were strongly associated with predator detection rates, suggesting these play a central role in canid foraging tactics by expediting movement. Consistent with expectations for prey contending with highly mobile predators, deer responses were more sensitive to proximal risk metrics at finer spatiotemporal scales, suggesting that coarser but more commonly used scales of analysis may miss useful insights into prey risk‐response. Time allocation appears to be a key tactic for deer risk management and was more strongly moderated by factors associated with forage or evasion heterogeneity (forest cover, snow and plant phenology) than factors associated with the likelihood of predator encounter (linear features). Trade‐offs between food and safety appeared to vary as much seasonally as spatially, with snow and vegetation phenology giving rise to a “phenology of fear.” Deer appear free to counter predators during milder times of year, but a combination of poor foraging state, reduced forage availability, greater movements costs, and reproductive state dampen responsiveness during winter. Pronounced intra‐annual variation in predator–prey interactions may be common in seasonal environments.

pystorms: A simulation sandbox for the development and evaluation of stormwater control algorithms - Sara P. Rimer; Abhiram Mullapudi; Sara C. Troutman; Gregory Ewing; Benjamin D. Bowes; Aaron A. Akin; Jeffrey Sadler; Ruben Kertesz; Bryant McDonnell; Luis Montestruque; Jon Hathaway; Jonathan L. Goodall; et al. (Environmental Modelling & Software, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

Effects of dolphin-swim activities on the behaviour of an Indo-Pacific bottlenose dolphin population off the south coast of Mozambique - Diana Rocha; Sarah A. Marley; Benjamin Drakeford; Jonathan Potts; Angie Gullan (Biological Conservation, 2023)

Effects of EU illegal logging policy on timber-supplying countries: A systematic review - Fredy D. Polo Villanueva; Yitagesu T. Tegegne; Georg Winkel; Paolo Omar Cerutti; Sabaheta Ramcilovic-Suominen; Constance L. McDermott; Jonathan Zeitlin; Metodi Sotirov; Benjamin Cashore; David Andrew Wardell; Andrew Haywood; Lukas Giessen (Journal of Environmental Management, 2023)

Intergenerational Interventions to Cultivate DEI-Champions: Increased Resilience and Accountability Through “Shipboard” Experiences - Raquel Bryant; Benjamin Keisling; Brian Starks; Bella Nunn; Lisa White; Jonathan Lewis; Sharon Cooper (Oceanography, 2023)
We developed All-ABOARD (Alliance Building Offshore to Achieve Resilience and Diversity) to meet the ever-increasing needs of cultivating a diverse geoscience workforce. All-ABOARD incorporates the Be the Messenger theoretical framework in all programmatic aspects to encourage participants to think about their own identities, positionalities, and privileges. Drawing from US-based institutions, we recruited four teams of four to five members who spanned a spectrum of positionality and career stages. To evaluate the efficacy of the program, we collected both quantitative and qualitative data at different intervals to measure changes in participants’ understanding and perception of identity, culture, respect, and diversity. The year-long core programming included regular webinars via Zoom and an in-person retreat. We found that immersive experiences and intergenerational teams led to the cultivation of a strong identity as a DEI-champion, enhanced group cohesion, and promoted feelings of resilience among participants. Our participants reported they felt most accountable to themselves and their teams, and that learning was accelerated by bringing together teams from multiple institutions to collaborate across intergenerational boundaries. Our program provides a model for training DEI-champions in geoscience who can advance strategic objectives in their home environments and demonstrates how frameworks from the social sciences can be effectively leveraged to transform geoscience.

A Review on Applications of Time-Lapse Electrical Resistivity Tomography Over the Last 30 Years : Perspectives for Mining Waste Monitoring - Adrien Dimech; LiZhen Cheng; Michel Chouteau; Jonathan Chambers; Sebastian Uhlemann; Paul Wilkinson; Philip Meldrum; Benjamin Mary; Gabriel Fabien-Ouellet; Anne Isabelle (Surveys in Geophysics, 2022)
Mining operations generate large amounts of wastes which are usually stored into large-scale storage facilities which pose major environmental concerns and must be properly monitored to manage the risk of catastrophic failures and also to control the generation of contaminated mine drainage. In this context, non-invasive monitoring techniques such as time-lapse electrical resistivity tomography (TL-ERT) are promising since they provide large-scale subsurface information that complements surface observations (walkover, aerial photogrammetry or remote sensing) and traditional monitoring tools, which often sample a tiny proportion of the mining waste storage facilities. The purposes of this review are as follows: (i) to understand the current state of research on TL-ERT for various applications; (ii) to create a reference library for future research on TL-ERT and geoelectrical monitoring mining waste; and (iii) to identify promising areas of development and future research needs on this issue according to our experience. This review describes the theoretical basis of geoelectrical monitoring and provides an overview of TL-ERT applications and developments over the last 30 years from a database of over 650 case studies, not limited to mining operations (e.g., landslide, permafrost). In particular, the review focuses on the applications of ERT for mining waste characterization and monitoring and a database of 150 case studies is used to identify promising applications for long-term autonomous geoelectrical monitoring of the geotechnical and geochemical stability of mining wastes. Potential challenges that could emerge from a broader adoption of TL-ERT monitoring for mining wastes are discussed. The review also considers recent advances in instrumentation, data acquisition, processing and interpretation for long-term monitoring and draws future research perspectives and promising avenues which could help improve the design and accuracy of future geoelectric monitoring programs in mining wastes.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Eyes and ears: A comparative approach linking the chemical composition of cod otoliths and eye lenses - Jonathan Stounberg; Tonny Bernt Thomsen; Benjamin Dominguez Heredia; Karin Hüssy (Journal of Fish Biology, 2022)
Fish eye lenses are a protein‐based chronological recorder of microchemical constituents that are a potentially useful tool for interpretations of environmental, ecological and life‐history experienced by fish. Here, we present the first study with data on the chemical composition of eye lenses from Baltic cod examined using laser ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) and compare these spatially resolved data to otoliths from the same fish also analysed by LA‐ICPMS, measuring the isotopes 27 Al, 137 Ba, 43 Ca, 52 Cr, 65 Cu, 57 Fe, 39 K, 7 Li, 25 Mg, 55 Mn, 31 P, 208 Pb, 85 Rb, 45 Sc, 29 Si, 88 Sr, 47 Ti, 50 V, 149 Yb, 66 Zn and 90 Zr. Comparison of the variation in element concentrations between eye lenses and otoliths from the same individuals showed minor similarities, suggesting a different governance in the uptake processes. A strong overlap between the concentric growth rings in the eye lenses and the otolith Sr periodicity was observed, where each consecutive minima in the chemical profile with high accuracy correspond to the width of each lens ring. No comparable trends were seen between growth rings and all other elements measured from both lenses and otoliths. The characteristic rings observed in cod eye lenses do not seem to represent seasonal fluctuation nor are they found to be directly linked to age. With this research, we provide a baseline study identifying elements in corresponding eye lenses and otoliths that show potential for unravelling the environmental and biological conditions experienced by fish.

The benefits of guide training for sustainable cetacean-based tourism in developing countries, case study – Ponta do Ouro Partial Marine Reserve, Mozambique - Diana Rocha; Sarah A. Marley; Benjamin Drakeford; Jonathan Potts; Angie Gullan (Journal of Coastal Conservation, 2022)
Tour guides represent the forefront of responsible Cetacean-Based Tourism (CBT), client satisfaction and product development. How an operation and specifically the guide facilitates the activity can shape tourists’ attitudes and change their behaviour towards the environment, turning consumers into stewards of the environment. This study examined the validity and success of a guide training workshop for CBT operators in the Ponta do Ouro Partial Marine Reserve (PPMR), Mozambique. A questionnaire survey was implemented pre- and post-training to measure the operators’ knowledge of aspects related to CBT and attitudes towards sustainable tourism and local regulations. Results suggest that the training workshop improved guide knowledge, which in some cases showed significant variations according to demographic variables namely, gender, education, and years of experience in the current job position. Mandatory guide training is recommended and should include not only product knowledge but also content on visitors’ expectations, interpretive guiding, and experience brokering. Presential training, refresher sessions, and English lessons are also advised. If these recommendations are put in place, then there is the potential for sustainable CBT to flourish in Mozambique, bringing much needed environmental and economic sustainability to this developing country.

Winter conditions structure extratropical patterns of species richness of amphibians, birds and mammals globally - David Gudex‐Cross; Likai Zhu; Spencer R. Keyser; Benjamin Zuckerberg; Jonathan N. Pauli; Volker C. Radeloff (Global Ecology and Biogeography, 2022)
Aim The aim was to derive global indices of winter conditions and examine their relationships with species richness patterns outside of the tropics. Location All extratropical areas (>25° N and 25° S latitudes), excluding islands. Time period 2000–2018. Major taxa studied Amphibians, birds and mammals. Methods We mapped three global indices of winter conditions [number of days of frozen ground (length of frozen ground winter); snow cover variability; and lack of subnivium (below‐snow refuge)] from satellite data, then used generalized additive models to examine their relationships with species richness patterns derived from range data. Results Length of frozen ground winter was the strongest predictor of species richness, with a consistent cross‐taxonomic decline in species richness occurring beyond 3 months of winter. It also often outperformed other environmental predictors of species richness patterns commonly used in biodiversity studies, including climate variables, primary productivity and elevation. In areas with ≥3 months of winter conditions, all three winter indices explained much of the deviance in amphibian, mammal and resident bird species richness. Mammals exhibited a stronger relationship with snow cover variability and lack of subnivium than the other taxa. Species richness of fully migratory species of birds peaked at c . 5.5 months of winter, coinciding with low species richness of residents. Main conclusions Our study demonstrates that winter structures latitudinal and elevational gradients of extratropical terrestrial species richness. In a rapidly warming world, tracking the seasonal dynamics of frozen ground and snow cover will be essential for predicting the consequences of climate change on species, communities and ecosystems. The indices of winter conditions we developed from satellite imagery provide an effective means of monitoring these dynamics into the future.

Significant suppression of invasive emerald ash borer by introduced parasitoids: potential for North American ash recovery - Jian J. Duan; Roy G. Van Driesche; Jonathan Schmude; Ryan Crandall; Claire Rutlege; Nicole Quinn; Benjamin H. Slager; Juli R. Gould; Joseph S. Elkinton (Journal of Pest Science, 2022)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Amphetamine alters an EEG marker of reward processing in humans and mice - James F. Cavanagh; Sarah L. Olguin; Jo A. Talledo; Juliana E. Kotz; Benjamin Z. Roberts; John A. Nungaray; Joyce Sprock; David Gregg; Savita G. Bhakta; Gregory A. Light; Neal R. Swerdlow; Jared W. Young; et al. (Psychopharmacology, 2022)

Isotopic and geochemical tracers of groundwater flow in the Shivwits Plateau, Grand Canyon National Park, USA - Jonathan W. Wilson; Andrea M. Erhardt; Benjamin W. Tobin (Hydrogeology Journal, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Spatial variation in bioclimatic relationships for a snow‐adapted species along a discontinuous southern range boundary - Sean M. Sultaire; John M. Humphreys; Benjamin Zuckerberg; Jonathan N. Pauli; Gary J. Roloff (Journal of Biogeography, 2022)
Aim Variation in the relationship between variables across space, known as spatial non‐stationarity, is a common phenomenon in ecology. Species distribution models (SDMs), however, typically assume stationarity in species–environment relationships across space. Spatial non‐stationarity may be particularly apparent in populations along range boundaries where species are actively adapting to changes in climate, and geographically isolated areas where isolation can facilitate adaptation. We used data collected from the southern range boundary of a winter‐adapted mammal to evaluate spatially varying environmental relationships in a region with a geographically isolated population. Taxon Lepus americanus . Location Laurentian Great Lakes region, USA. Methods We surveyed 320 sites for snowshoe hares near their regional southern range boundary. We related snowshoe hare occurrence to short‐term climate variables (snow cover duration, maximum temperature and their interaction) with a spatially explicit model that allowed the effect of climate variables on snowshoe hare occurrence to vary spatially. Results We found highest support for an SDM that incorporated geographic barriers when estimating spatial effects, in addition to spatially varying effects of maximum temperate, snow cover duration and their interaction. Hares were more likely to occupy sites with longer snow cover duration but the influence of temperature was more variable. Increasing temperature in northern portions of our study area had a positive influence on hare occurrence, but exhibited a negative relationship along the southern range boundary. Main Conclusions We provide a robust evaluation of stationarity assumptions in bioclimatic relationships and highlight spatially variable relationships between a cold‐adapted species and short‐term climate variables across a range boundary. However, spatial non‐stationarity was not most apparent across dispersal barriers but coincided with differences in the relationship between climate variables across space. Our study provides evidence that the distribution of a winter‐adapted species is strongly constrained by snow cover, but prevailing temperature modulates the strength of this relationship across space.

Oklahoma Nathan Shock Aging Center — assessing the basic biology of aging from genetics to protein and function - Holly Van Remmen; Willard M. Freeman; Benjamin F. Miller; Michael Kinter; Jonathan D. Wren; Ann Chiao; Rheal A. Towner; Timothy A. Snider; William E. Sonntag; Arlan Richardson (GeroScience, 2021)

A global reconnaissance of particulates and metals/metalloids in untreated drinking water sources - Jonathan W. Peterson; Benjamin M. Fry; Daniel R. Wade; Ford J. Fishman; Jacob T. Stid; Jonas M. Peterson; Cleveland E. Tarp; Randall D. Wade; Sarah A. Brokus; Michael J. Pikaart; Brent P. Krueger; Aaron A. Best (Environmental Monitoring and Assessment, 2021)
Metal and metalloid contamination in drinking water sources is a global concern, particularly in developing countries. This study used hollow membrane water filters and metal-capturing polyurethane foams to sample 71 drinking water sources in 22 different countries. Field sampling was performed with sampling kits prepared in the lab at Hope College in Holland, MI, USA. Filters and foams were sent back to the lab after sampling, and subsequent analysis of flushates and rinsates allowed the estimation of suspended solids and metal and other analayte concentrations in source waters. Estimated particulate concentrations were 0–92 mg/L, and consisted of quartz, feldspar, and clay, with some samples containing metal oxides or sulfide phases. As and Cu were the only analytes which occurred above the World Health Organization (WHO) guidelines of 10 μg/L and 2000 μg/L, respectively, with As exceeding the guideline in 45% of the sources and Cu in 3%. Except for one value of ~ 285 μg/L, As concentrations were 45–200 μg/L (river), 65–179 μg/L (well), and 112–178 μg/L (tap). Other metals (Ce, Fe, Mg, Mn, Zn) with no WHO guideline were also detected, with Mn the most common. This study demonstrated that filters and foams can be used for reconnaissance characterization of untreated drinking water. However, estimated metal and other analyte concentrations could only be reported as minimum values due to potential incomplete retrieval of foam-bound analytes. A qualitative reporting methodology was used to report analytes as “present” if the concentration was below the WHO guideline, and “present-recommend retesting” if the concentration was quantifiable and above the WHO guideline.

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Tundra wildfire triggers sustained lateral nutrient loss in Alaskan Arctic - Benjamin W. Abbott; Adrian V. Rocha; Arial Shogren; Jay P. Zarnetske; Frances Iannucci; William B. Bowden; Samuel P. Bratsman; Leika Patch; Rachel Watts; Randy Fulweber; Rebecca J. Frei; Amanda M. Huebner; et al. (Global Change Biology, 2021)
Climate change is creating widespread ecosystem disturbance across the permafrost zone, including a rapid increase in the extent and severity of tundra wildfire. The expansion of this previously rare disturbance has unknown consequences for lateral nutrient flux from terrestrial to aquatic environments. Lateral loss of nutrients could reduce carbon uptake and slow recovery of already nutrient‐limited tundra ecosystems. To investigate the effects of tundra wildfire on lateral nutrient export, we analyzed water chemistry in and around the 10‐year‐old Anaktuvuk River fire scar in northern Alaska. We collected water samples from 21 burned and 21 unburned watersheds during snowmelt, at peak growing season, and after plant senescence in 2017 and 2018. After a decade of ecosystem recovery, aboveground biomass had recovered in burned watersheds, but overall carbon and nitrogen remained ~20% lower, and the active layer remained ~10% deeper. Despite lower organic matter stocks, dissolved organic nutrients were substantially elevated in burned watersheds, with higher flow‐weighted concentrations of organic carbon (25% higher), organic nitrogen (59% higher), organic phosphorus (65% higher), and organic sulfur (47% higher). Geochemical proxies indicated greater interaction with mineral soils in watersheds with surface subsidence, but optical analysis and isotopes suggested that recent plant growth, not mineral soil, was the main source of organic nutrients in burned watersheds. Burned and unburned watersheds had similar δ 15 N‐NO 3 − , indicating that exported nitrogen was of preburn origin (i.e., not recently fixed). Lateral nitrogen flux from burned watersheds was 2‐ to 10‐fold higher than rates of background nitrogen fixation and atmospheric deposition estimated in this area. These findings indicate that wildfire in Arctic tundra can destabilize nitrogen, phosphorus, and sulfur previously stored in permafrost via plant uptake and leaching. This plant‐mediated nutrient loss could exacerbate terrestrial nutrient limitation after disturbance or serve as an important nutrient release mechanism during succession.

The Use of Animal-Borne Biologging and Telemetry Data to Quantify Spatial Overlap of Wildlife with Marine Renewables - Natalie Isaksson; Ian R. Cleasby; Ellie Owen; Benjamin J. Williamson; Jonathan D. R. Houghton; Jared Wilson; Elizabeth A. Masden (Journal of Marine Science and Engineering, 2021)
The growth of the marine renewable energy sector requires the potential effects on marine wildlife to be considered carefully. For this purpose, utilization distributions derived from animal-borne biologging and telemetry data provide accurate information on individual space use. The degree of spatial overlap between potentially vulnerable wildlife such as seabirds and development areas can subsequently be quantified and incorporated into impact assessments and siting decisions. While rich in information, processing and analyses of animal-borne tracking data are often not trivial. There is therefore a need for straightforward and reproducible workflows for this technique to be useful to marine renewables stakeholders. The aim of this study was to develop an analysis workflow to extract utilization distributions from animal-borne biologging and telemetry data explicitly for use in assessment of animal spatial overlap with marine renewable energy development areas. We applied the method to European shags (Phalacrocorax aristotelis) in relation to tidal stream turbines. While shag occurrence in the tidal development area was high (99.4%), there was no overlap (0.14%) with the smaller tidal lease sites within the development area. The method can be applied to any animal-borne bio-tracking datasets and is relevant to stakeholders aiming to quantify environmental effects of marine renewables.

Plio‐Pleistocene environmental changes shape present day phylogeography of New Zealand's southern beeches (Nothofagaceae) - Nicolas J. Rawlence; Benjamin C. M. Potter; Nic Dussex; Lachie Scarsbrook; David A. Orlovich; Jonathan M. Waters; Matt McGlone; Michael Knapp (New Zealand Journal of Botany, 2021)
Island ecosystems can be severely affected by climate change as they provide limited opportunities for species to track their habitat. Studying the population dynamics of keystone species from these ecosystems can shed a light on climate – ecosystem interactions. Southern beeches are such keystone species in New Zealand with beech forests constituting the most abundant forest cover on the two main islands. Here we use 2.4 kilobase pairs of chloroplast genetic markers from four species of southern beech across their geographic distribution to help elucidate the Pleistocene history of New Zealand forests, and the processes that led to the present‐day distribution of southern beech diversity. Broadly concordant phylogeographic patterns were observed across all beech species analysed. The centre of genetic diversity in silver beech was in the northern South Island, with unique haplotypes in the southern South Island, and southern and northern North Island, separated by known ‘beech gaps’. Significantly less genetic diversity was evident in the subgenus Fuscospora (red, hard, black/mountain beech). All three species shared a single haplotype in the southern South Island, and a unique haplotype north of the central South Island ‘beech gap’. Our study indicates that the present‐day distribution of southern beech diversity in New Zealand is largely a result of Plio‐Pleistocene environmental changes, with survival in cryptic southern South Island and multiple North Island in situ microrefugia throughout recent glacial cycles. By contrast, the northern South Island was likely the only New Zealand region that supported large (silver) beech populations throughout the Pleistocene. With beech species in New Zealand being keystone forest species, the distribution of the genus throughout the Pleistocene provides a proxy for forest cover at different times. It helps understand the ecological challenges the New Zealand forest fauna and flora were exposed to during the climate oscillations of the ice ages.

Characterization of strains of Chlorella from Abakaliki, Nigeria, for the production of high-value products under variable temperatures - John Nwkpuru Idenyi; Jonathan Chukwu Eya; James Chukwuma Ogbonna; Mathias Ahii Chia; Md Asraful Alam; Benjamin E. Ubi (Journal of Applied Phycology, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

High-Resolution Sampling of a Broad Marine Life Size Spectrum Reveals Differing Size- and Composition-Based Associations With Physical Oceanographic Structure - Adam T. Greer; John C. Lehrter; Benjamin M. Binder; Aditya R. Nayak; Ranjoy Barua; Ana E. Rice; Jonathan H. Cohen; Malcolm N. McFarland; Alexis Hagemeyer; Nicole D. Stockley; Kevin M. Boswell; Igor Shulman; et al. (Frontiers in Marine Science, 2020)
Observing multiple size classes of organisms, along with oceanographic properties and water mass origins, can improve our understanding of the drivers of aggregations, yet acquiring these measurements remains a fundamental challenge in biological oceanography. By deploying multiple biological sampling systems, from conventional bottle and net sampling to in situ imaging and acoustics, we describe the spatial patterns of different size classes of marine organisms (several microns to ∼10 cm) in relation to local and regional (m to km) physical oceanographic conditions on the Delaware continental shelf. The imaging and acoustic systems deployed included (in ascending order of target organism size) an imaging flow cytometer (CytoSense), a digital holographic imaging system (HOLOCAM), an In Situ Ichthyoplankton Imaging System (ISIIS, 2 cameras with different pixel resolutions), and multi-frequency acoustics (SIMRAD, 18 and 38 kHz). Spatial patterns generated by the different systems showed size-dependent aggregations and differing connections to horizontal and vertical salinity and temperature gradients that would not have been detected with traditional station-based sampling (∼9-km resolution). A direct comparison of the two ISIIS cameras showed composition and spatial patchiness changes that depended on the organism size, morphology, and camera pixel resolution. Large zooplankton near the surface, primarily composed of appendicularians and gelatinous organisms, tended to be more abundant offshore near the shelf break. This region was also associated with high phytoplankton biomass and higher overall organism abundances in the ISIIS, acoustics, and targeted net sampling. In contrast, the inshore region was dominated by hard-bodied zooplankton and had relatively low acoustic backscatter. The nets showed a community dominated by copepods, but they also showed high relative abundances of soft-bodied organisms in the offshore region where these organisms were quantified by the ISIIS. The HOLOCAM detected dense patches of ciliates that were too small to be captured in the nets or ISIIS imagery. This near-simultaneous deployment of different systems enables the description of the spatial patterns of different organism size classes, their spatial relation to potential prey and predators, and their association with specific oceanographic conditions. These datasets can also be used to evaluate the efficacy of sampling techniques, ultimately aiding in the design of efficient, hypothesis-driven sampling programs that incorporate these complementary technologies.

Agricultural impacts of climate change in Indiana and potential adaptations - Laura C. Bowling; Keith A. Cherkauer; Charlotte I. Lee; Janna L. Beckerman; Sylvie Brouder; Jonathan R. Buzan; Otto C. Doering; Jeffrey S. Dukes; Paul D. Ebner; Jane R. Frankenberger; Benjamin M. Gramig; Eileen J. Kladivko; et al. (Climatic Change, 2020)

Future winters present a complex energetic landscape of decreased costs and reduced risk for a freeze‐tolerant amphibian, the Wood Frog ( Lithobates sylvaticus ) - Megan J. Fitzpatrick; Warren P. Porter; Jonathan N. Pauli; Michael R. Kearney; Michael Notaro; Benjamin Zuckerberg (Global Change Biology, 2020)
Winter climate warming is rapidly leading to changes in snow depth and soil temperatures across mid‐ and high‐latitude ecosystems, with important implications for survival and distribution of species that overwinter beneath the snow. Amphibians are a particularly vulnerable group to winter climate change because of the tight coupling between their body temperature and metabolic rate. Here, we used a mechanistic microclimate model coupled to an animal biophysics model to predict the spatially explicit effects of future climate change on the wintering energetics of a freeze‐tolerant amphibian, the Wood Frog ( Lithobates sylvaticus ), across its distributional range in the eastern United States. Our below‐the‐snow microclimate simulations were driven by dynamically downscaled climate projections from a regional climate model coupled to a one‐dimensional model of the Laurentian Great Lakes. We found that warming soil temperatures and decreasing winter length have opposing effects on Wood Frog winter energy requirements, leading to geographically heterogeneous implications for Wood Frogs. While energy expenditures and peak body ice content were predicted to decline in Wood Frogs across most of our study region, we identified an area of heightened energetic risk in the northwestern part of the Great Lakes region where energy requirements were predicted to increase. Because Wood Frogs rely on body stores acquired in fall to fuel winter survival and spring breeding, increased winter energy requirements have the potential to impact local survival and reproduction. Given the geographically variable and intertwined drivers of future under‐snow conditions (e.g., declining snow depths, rising air temperatures, shortening winters), spatially explicit assessments of species energetics and risk will be important to understanding the vulnerability of subnivium‐adapted species.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Landslides across the USA: occurrence, susceptibility, and data limitations - Benjamin B. Mirus; Eric S. Jones; Rex L. Baum; Jonathan W. Godt; Stephen Slaughter; Matthew M. Crawford; Jeremy Lancaster; Thomas Stanley; Dalia B. Kirschbaum; William J. Burns; Robert G. Schmitt; Kassandra O. Lindsey; et al. (Landslides, 2020)
Detailed information about landslide occurrence is the foundation for advancing process understanding, susceptibility mapping, and risk reduction. Despite the recent revolution in digital elevation data and remote sensing technologies, landslide mapping remains resource intensive. Consequently, a modern, comprehensive map of landslide occurrence across the United States (USA) has not been compiled. As a first step toward this goal, we present a national-scale compilation of existing, publicly available landslide inventories. This geodatabase can be downloaded in its entirety or viewed through an online, searchable map, with parsimonious attributes and direct links to the contributing sources with additional details. The mapped spatial pattern and concentration of landslides are consistent with prior characterization of susceptibility within the conterminous USA, with some notable exceptions on the West Coast. Although the database is evolving and known to be incomplete in many regions, it confirms that landslides do occur across the country, thus highlighting the importance of our national-scale assessment. The map illustrates regions where high-quality mapping has occurred and, in contrast, where additional resources could improve confidence in landslide characterization. For example, borders between states and other jurisdictions are quite apparent, indicating the variation in approaches to data collection by different agencies and disparity between the resources dedicated to landslide characterization. Further investigations are needed to better assess susceptibility and to determine whether regions with high relief and steep topography, but without mapped landslides, require further landslide inventory mapping. Overall, this map provides a new resource for accessing information about known landslides across the USA.

The value of climate-resilient seeds for smallholder adaptation in sub-Saharan Africa - Oscar J. Cacho; Jonathan Moss; Philip K. Thornton; Mario Herrero; Ben Henderson; Benjamin L. Bodirsky; Florian Humpenöder; Alexander Popp; Leslie Lipper (Climatic Change, 2020)
Climate change is threatening food security in many tropical countries, where a large proportion of food is produced by vulnerable smallholder farmers. Interventions are available to offset many of the negative impacts of climate change on agriculture, and they can be tailored to local conditions often through relative modest investments. However, little quantitative information is available to guide investment or policy choices at a time when countries and development agencies are under pressure to implement policies that can help achieve Sustainable Development Goals while coping with climate change. Among smallholder adaptation options, developing seeds resilient to current and future climate shocks expected locally is one of the most important actions available now. In this paper, we used national and local data to estimate the costs of climate change to smallholder farmers in Malawi and Tanzania. We found that the benefits from adopting resilient seeds ranged between 984 million and 2.1 billion USD during 2020–2050. Our analysis demonstrates the benefits of establishing and maintaining a flexible national seed sector with participation by communities in the breeding, delivery, and adoption cycle.

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

A trophic cascade initiated by an invasive vertebrate alters the structure of native reptile communities - Benjamin Feit; Tim Dempster; Tim S. Jessop; Jonathan K. Webb; Mike Letnic (Global Change Biology, 2020)
Invasive vertebrates are frequently reported to have catastrophic effects on the populations of species which they directly impact. It follows then, that if invaders exert strong suppressive effects on some species then other species will indirectly benefit due to ecological release from interactions with directly impacted species. However, evidence that invasive vertebrates trigger such trophic cascades and alter community structure in terrestrial ecosystems remains rare. Here, we ask how the cane toad, a vertebrate invader that is toxic to many of Australia's vertebrate predators, influences lizard assemblages in a semi‐arid rangeland. In our study area, the density of cane toads is influenced by the availability of water accessible to toads. We compared an index of the abundance of sand goannas, a large predatory lizard that is susceptible to poisoning by cane toads and the abundances of four lizard families preyed upon by goannas (skinks, pygopods, agamid lizards and geckos) in areas where cane toads were common or rare. Consistent with the idea that suppression of sand goannas by cane toads initiates a trophic cascade, goanna activity was lower and small lizards were more abundant where toads were common. The hypothesis that suppression of sand goannas by cane toads triggers a trophic cascade was further supported by our findings that small terrestrial lizards that are frequently preyed upon by goannas were more affected by toad abundance than arboreal geckos, which are rarely consumed by goannas. Furthermore, the abundance of at least one genus of terrestrial skinks benefitted from allogenic ecosystem engineering by goannas where toads were rare. Overall, our study provides evidence that the invasion of ecosystems by non‐native species can have important effects on the structure and integrity of native communities extending beyond their often most obvious and frequently documented direct ecological effects.

Inflammation-associated suppression of metabolic gene networks in acute and chronic liver disease - Gisela Campos; Wolfgang Schmidt-Heck; Jonathan De Smedt; Agata Widera; Ahmed Ghallab; Larissa Pütter; Daniela González; Karolina Edlund; Cristina Cadenas; Rosemarie Marchan; Reinhard Guthke; Catherine Verfaillie; et al. (Archives of Toxicology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Shifting perceptions of rapid temperature changes’ effects on marine fisheries, 1945–2017 - Loren McClenachan; Jonathan H. Grabowski; Madison Marra; C. Seabird McKeon; Benjamin P. Neal; Nicholas R. Record; Steven B. Scyphers (Fish and Fisheries, 2019)
Climate‐driven warming has both social and ecological effects on marine fisheries. While recent changes due to anthropogenic global warming have been documented, similar basin‐wide changes have occurred in the past due to natural temperature fluctuations. Here, we document the effects of rapidly changing water temperatures along the United States’ east coast using observations from fisheries newspapers during a warming phase (1945–1951) and subsequent cooling phase (1952–1960) of the Atlantic Multidecadal Oscillation, which we compared to similar recent observations of warming waters (1998–2017). Historical warming and cooling events affected the abundance of species targeted by fishing, the prevalence of novel and invasive species, and physical access to targeted species. Fishing communities viewed historical cooling waters twice as negatively as they did warming waters (72% vs. 35% of observations). Colder waters were associated with a decrease in fishing opportunity due to storminess, while warming waters were associated with the potential for new fisheries. In contrast, recent warming waters were viewed as strongly negative by fishing communities (72% of observations), associated with disease, reductions in abundances of target species, and shifts in distributions across jurisdictional lines. This increasing perception that warming negatively affects local fisheries may be due to an overall reduction of opportunity in fisheries over the past half century, an awareness of the relative severity of warming today, larger changes in American culture, or a combination of these factors. Negative perceptions of recent warming waters’ effects on fisheries suggest that fishing communities are currently finding the prospect of climate adaptation difficult.

Southern African summer-rainfall variability, and its teleconnections, on interannual to interdecadal timescales in CMIP5 models - Bastien Dieppois; Benjamin Pohl; Julien Crétat; Jonathan Eden; Moussa Sidibe; Mark New; Mathieu Rouault; Damian Lawler (Climate Dynamics, 2019)

Tropical rainforest flies carrying pathogens form stable associations with social nonhuman primates - Jan F. Gogarten; Ariane Düx; Benjamin Mubemba; Kamilla Pléh; Constanze Hoffmann; Alexander Mielke; Jonathan Müller‐Tiburtius; Andreas Sachse; Roman M. Wittig; Sébastien Calvignac‐Spencer; Fabian H. Leendertz (Molecular Ecology, 2019)
Living in groups provides benefits but also incurs costs such as attracting disease vectors. For example, synanthropic flies associate with human settlements, and higher fly densities increase pathogen transmission. We investigated whether such associations also exist in highly mobile nonhuman primate (NHP) Groups. We studied flies in a group of wild sooty mangabeys ( Cercocebus atys atys ) and three communities of wild chimpanzees ( Pan troglodytes verus ) in Taï National Park, Côte d'Ivoire. We observed markedly higher fly densities within both mangabey and chimpanzee groups. Using a mark–recapture experiment, we showed that flies stayed with the sooty mangabey group for up to 12 days and for up to 1.3 km. We also tested mangabey‐associated flies for pathogens infecting mangabeys in this ecosystem, Bacillus cereus biovar anthracis ( Bc bv a ), causing sylvatic anthrax, and Treponema pallidum pertenue , causing yaws. Flies contained treponemal (6/103) and Bc bv a (7/103) DNA. We cultured Bc bv a from all PCR‐positive flies, confirming bacterial viability and suggesting that this bacterium might be transmitted and disseminated by flies. Whole genome sequences of Bc bv a isolates revealed a diversity of Bc bv a , probably derived from several sources. We conclude that flies actively track mangabeys and carry infectious bacterial pathogens; these associations represent an understudied cost of sociality and potentially expose many social animals to a diversity of pathogens.

Snow roosting reduces temperature-associated stress in a wintering bird - Amy A. Shipley; Michael J. Sheriff; Jonathan N. Pauli; Benjamin Zuckerberg (Oecologia, 2019)

Correction to: Widespread colonisation of Tanzanian catchments by introduced Oreochromis tilapia fishes: the legacy from decades of deliberate introduction - Asilatu Shechonge; Benjamin P. Ngatunga; Stephanie J. Bradbeer; Julia J. Day; Jennifer J. Freer; Antonia G. P. Ford; Jonathan Kihedu; Tabitha Richmond; Semvua Mzighani; Alan M. Smith; Emmanuel A. Sweke; Rashid Tamatamah; et al. (Hydrobiologia, 2019)

Widespread colonisation of Tanzanian catchments by introduced Oreochromis tilapia fishes: the legacy from decades of deliberate introduction - Asilatu Shechonge; Benjamin P. Ngatunga; Stephanie J. Bradbeer; Julia J. Day; Jennifer J. Freer; Antonia G. P. Ford; Jonathan Kihedu; Tabitha Richmond; Semvua Mzighani; Alan M. Smith; Emmanuel A. Sweke; Rashid Tamatamah; et al. (Hydrobiologia, 2019)

Value of protected areas to avian persistence across 20 years of climate and land‐use change - Michelle A. Peach; Jonathan B. Cohen; Jacqueline L. Frair; Benjamin Zuckerberg; Patrick Sullivan; William F. Porter; Corey Lang (Conservation Biology, 2019)
Establishing protected areas, where human activities and land cover changes are restricted, is among the most widely used strategies for biodiversity conservation. This practice is based on the assumption that protected areas buffer species from processes that drive extinction. However, protected areas can maintain biodiversity in the face of climate change and subsequent shifts in distributions have been questioned. We evaluated the degree to which protected areas influenced colonization and extinction patterns of 97 avian species over 20 years in the northeastern United States. We fitted single‐visit dynamic occupancy models to data from Breeding Bird Atlases to quantify the magnitude of the effect of drivers of local colonization and extinction (e.g., climate, land cover, and amount of protected area) in heterogeneous landscapes that varied in the amount of area under protection. Colonization and extinction probabilities improved as the amount of protected area increased, but these effects were conditional on landscape context and species characteristics. In this forest‐dominated region, benefits of additional land protection were greatest when both forest cover in a grid square and amount of protected area in neighboring grid squares were low. Effects did not vary with species’ migratory habit or conservation status. Increasing the amounts of land protection benefitted the range margins species but not the core range species. The greatest improvements in colonization and extinction rates accrued for forest birds relative to open‐habitat or generalist species. Overall, protected areas stemmed extinction more than they promoted colonization. Our results indicate that land protection remains a viable conservation strategy despite changing habitat and climate, as protected areas both reduce the risk of local extinction and facilitate movement into new areas. Our findings suggest conservation in the face of climate change favors creation of new protected areas over enlarging existing ones as the optimal strategy to reduce extinction and provide stepping stones for the greatest number of species.

Range change evolution of peat mosses ( Sphagnum ) within and between climate zones - A. Jonathan Shaw; Benjamin E. Carter; Blanka Aguero; Denise Pinheiro da Costa; Andrew A. Crowl (Global Change Biology, 2019)
Peat mosses ( Sphagnum ) hold exceptional importance in the control of global carbon fluxes and climate because of the vast stores of carbon bound up in partially decomposed biomass (peat). This study tests the hypothesis that the early diversification of Sphagnum was in the Northern Hemisphere, with subsequent range expansions to tropical latitudes and the Southern Hemisphere. A phylogenetic analysis of 192 accessions representing the moss class Sphagnopsida based on four plastid loci was conducted in conjunction with biogeographic analyses using BioGeoBEARS to investigate the tempo and mode of geographic range evolution. Analyses support the hypothesis that the major intrageneric clades of peat‐forming species accounting for >90% of peat moss diversity originated and diversified at northern latitudes. The genus underwent multiple range expansions into tropical and Southern Hemisphere regions. Range evolution in peat mosses was most common within latitudinal zones, attesting to the relative difficulty of successfully invading new climate zones. Allopolyploidy in Sphagnum (inferred from microsatellite heterozygosity) does not appear to be biased with regard to geographic region nor intrageneric clade. The inference that Sphagnum diversified in cool‐or cold‐climate regions and repeatedly expanded its range into tropical regions makes the genus an excellent model for studying morphological, physiological, and genomic traits associated with adaptation to warming climates.

Microbes follow Humboldt: temperature drives plant and soil microbial diversity patterns from the Amazon to the Andes - Andrew T. Nottingham; Noah Fierer; Benjamin L. Turner; Jeanette Whitaker; Nick J. Ostle; Niall P. McNamara; Richard D. Bardgett; Jonathan W. Leff; Norma Salinas; Miles R. Silman; Loeske E. B. Kruuk; Patrick Meir (Ecology, 2018)
More than 200 years ago, Alexander von Humboldt reported that tropical plant species richness decreased with increasing elevation and decreasing temperature. Surprisingly, coordinated patterns in plant, bacterial, and fungal diversity on tropical mountains have not yet been observed, despite the central role of soil microorganisms in terrestrial biogeochemistry and ecology. We studied an Andean transect traversing 3.5 km in elevation to test whether the species diversity and composition of tropical forest plants, soil bacteria, and fungi follow similar biogeographical patterns with shared environmental drivers. We found coordinated changes with elevation in all three groups: species richness declined as elevation increased, and the compositional dissimilarity among communities increased with increased separation in elevation, although changes in plant diversity were larger than in bacteria and fungi. Temperature was the dominant driver of these diversity gradients, with weak influences of edaphic properties, including soil pH . The gradients in microbial diversity were strongly correlated with the activities of enzymes involved in organic matter cycling, and were accompanied by a transition in microbial traits towards slower‐growing, oligotrophic taxa at higher elevations. We provide the first evidence of coordinated temperature‐driven patterns in the diversity and distribution of three major biotic groups in tropical ecosystems: soil bacteria, fungi, and plants. These findings suggest that interrelated and fundamental patterns of plant and microbial communities with shared environmental drivers occur across landscape scales. These patterns are revealed where soil pH is relatively constant, and have implications for tropical forest communities under future climate change.

A Quantitative Assessment of the Annual Contribution of Platform Downwearing to Beach Sediment Budget: Happisburgh, England, UK - Andres Payo; Mike Walkden; Michael A. Ellis; Andrew Barkwith; David Favis-Mortlock; Holger Kessler; Benjamin Wood; Helen Burke; Jonathan Lee (Journal of Marine Science and Engineering, 2018)
Field and numerical investigations at Happisburgh, East coast of England, UK, sought to characterize beach thickness and determine geologic framework controls on coastal change. After a major failure of coastal protection infrastructure, removal of about 1 km of coastal defence along the otherwise protected cliffed coastline of Happisburgh triggered a period of rapid erosion over 20 years of ca. 140 m. Previous sensitivity studies suggest that beach thickness plays a major role in coastal recession. These studies were limited, however, by a lack of beach volume data. In this study, we have integrated the insights gained from our understanding of the Quaternary geology of the area, a novel non-intrusive passive seismic survey method, and a 3D novel representation of the subsurface source and transportable material into a coastal modelling environment to explore the role of beach thickness on the back wearing and downwearing of the cliffs and consolidated platform, respectively. Results show that beach thickness is non-homogeneous along the study site: we estimate that the contribution to near-shore sediment budget via platform downwearing is of a similar order of magnitude as sediment lost from the beach and therefore non-negligible. We have provided a range of evidence to support the idea that the Happisburgh beach is a relatively thin layer perched on a sediment rich platform of sand and gravel. This conceptualization differs from previous publications, which assume that the platform was mostly till and fine material. This has direct implication on regional sediment management along this coastline. The present study contributes to our understanding of a poorly known aspect of coastal sediment budgeting and outlines a quantitative approach that allows for simple integration of geological understanding for coastline evolution assessments worldwide.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

Conserving and managing the subnivium - Benjamin Zuckerberg; Jonathan N. Pauli (Conservation Biology, 2018)
In regions where snowfall historically has been a defining seasonal characteristic of the landscape, warming winters have reduced the depth, duration, and extent of snowpack. However, most management and conservation has focused on how aboveground wildlife will be affected by altered snow conditions, even though the majority of species that persist through the winter do so under the snowpack in a thermally stable refugium: the subnivium. Shortened winters, forest management practices, and winter recreation can alter subnivium conditions by increasing snow compaction and compromising thermal stability at the soil–snow interface. To help slow the loss of the subnivium in the face of rapidly changing winter conditions, we suggest managers adopt regional conservation plans for identifying threatened snow‐covered environments; measure and predict the effects land cover and habitat management has on local subnivium conditions; and control the timing and distribution of activities that disturb and compact snow cover (e.g., silvicultural practices, snow recreation, and road and trail maintenance). As a case study, we developed a spatially explicit model of subnivium presence in a working landscape of the Chequamegon National Forest, Wisconsin. We identified landscapes where winter recreation and management practices could threaten potentially important areas for subnivium persistence. Similar modeling approaches could inform management decisions related to subnivium conservation. Current climate projections predict that snow seasons will change rapidly in many regions, and as result, we advocate for the immediate recognition, conservation, and management of the subnivium and its dependent species.

Variability in soil-water retention properties and implications for physics-based simulation of landslide early warning criteria - Matthew A. Thomas; Benjamin B. Mirus; Brian D. Collins; Ning Lu; Jonathan W. Godt (Landslides, 2018)

Invasive cane toads might initiate cascades of direct and indirect effects in a terrestrial ecosystem - Benjamin Feit; Christopher E. Gordon; Jonathan K. Webb; Tim S. Jessop; Shawn W. Laffan; Tim Dempster; Mike Letnic (Biological Invasions, 2018)

Large uncertainty in carbon uptake potential of land‐based climate‐change mitigation efforts - Andreas Krause; Thomas A. M. Pugh; Anita D. Bayer; Wei Li; Felix Leung; Alberte Bondeau; Jonathan C. Doelman; Florian Humpenöder; Peter Anthoni; Benjamin L. Bodirsky; Philippe Ciais; Christoph Müller; et al. (Global Change Biology, 2018)
Most climate mitigation scenarios involve negative emissions, especially those that aim to limit global temperature increase to 2°C or less. However, the carbon uptake potential in land‐based climate change mitigation efforts is highly uncertain. Here, we address this uncertainty by using two land‐based mitigation scenarios from two land‐use models ( IMAGE and MA g PIE ) as input to four dynamic global vegetation models ( DGVM s; LPJ ‐ GUESS , ORCHIDEE , JULES , LPJ mL). Each of the four combinations of land‐use models and mitigation scenarios aimed for a cumulative carbon uptake of ~130 GtC by the end of the century, achieved either via the cultivation of bioenergy crops combined with carbon capture and storage ( BECCS ) or avoided deforestation and afforestation ( ADAFF ). Results suggest large uncertainty in simulated future land demand and carbon uptake rates, depending on the assumptions related to land use and land management in the models. Total cumulative carbon uptake in the DGVM s is highly variable across mitigation scenarios, ranging between 19 and 130 GtC by year 2099. Only one out of the 16 combinations of mitigation scenarios and DGVM s achieves an equivalent or higher carbon uptake than achieved in the land‐use models. The large differences in carbon uptake between the DGVM s and their discrepancy against the carbon uptake in IMAGE and MA g PIE are mainly due to different model assumptions regarding bioenergy crop yields and due to the simulation of soil carbon response to land‐use change. Differences between land‐use models and DGVM s regarding forest biomass and the rate of forest regrowth also have an impact, albeit smaller, on the results. Given the low confidence in simulated carbon uptake for a given land‐based mitigation scenario, and that negative emissions simulated by the DGVM s are typically lower than assumed in scenarios consistent with the 2°C target, relying on negative emissions to mitigate climate change is a highly uncertain strategy.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Widespread Degradation of a Vernal Pool Network in the Southeastern United States: Challenges to Current and Future Management - Jonathan P. Evans; Kristen K. Cecala; Brett R. Scheffers; Callie A. Oldfield; Nicholas A. Hollingshead; David G. Haskell; Benjamin A. McKenzie (Wetlands, 2017)

Role of DNA methylation in the dietary restriction mediated cellular memory - Archana Unnikrishnan; Jordan Jackson; Stephanie A. Matyi; Niran Hadad; Benjamin Wronowski; Constantin Georgescu; Karla P. Garrett; Jonathan D. Wren; Willard M. Freeman; Arlan Richardson (GeroScience, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

The Interplay Between Landscape Structure and Biotic Interactions - Phoebe L. Zarnetske; Benjamin Baiser; Angela Strecker; Sydne Record; Jonathan Belmaker; Mao-Ning Tuanmu (Current Landscape Ecology Reports, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Immortalization of primary microglia: a new platform to study HIV regulation in the central nervous system - Yoelvis Garcia-Mesa; Taylor R. Jay; Mary Ann Checkley; Benjamin Luttge; Curtis Dobrowolski; Saba Valadkhan; Gary E. Landreth; Jonathan Karn; David Alvarez-Carbonell (Journal of NeuroVirology, 2017)

Connectivity between the central nucleus of the amygdala and the bed nucleus of the stria terminalis in the non-human primate: neuronal tract tracing and developmental neuroimaging studies - Jonathan A. Oler; Do P. M. Tromp; Andrew S. Fox; Rothem Kovner; Richard J. Davidson; Andrew L. Alexander; Daniel R. McFarlin; Rasmus M. Birn; Benjamin E. Berg; Danielle M. deCampo; Ned H. Kalin; Julie L. Fudge (Brain Structure and Function, 2017)

Infection risk decreases with increasing mismatch in host and pathogen environmental tolerances - A. Justin Nowakowski; Steven M. Whitfield; Evan A. Eskew; Michelle E. Thompson; Jonathan P. Rose; Benjamin L. Caraballo; Jacob L. Kerby; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2016)
The fungal pathogen Batrachochytrium dendrobatidis ( Bd ) has caused the greatest known wildlife pandemic, infecting over 500 amphibian species. It remains unclear why some host species decline from disease‐related mortality whereas others persist. We introduce a conceptual model that predicts that infection risk in ectotherms will decrease as the difference between host and pathogen environmental tolerances (i.e. tolerance mismatch) increases. We test this prediction using both local‐scale data from Costa Rica and global analyses of over 11 000 Bd infection assays. We find that infection prevalence decreases with increasing thermal tolerance mismatch and with increasing host tolerance of habitat modification. The relationship between environmental tolerance mismatches and Bd infection prevalence is generalisable across multiple amphibian families and spatial scales, and the magnitude of the tolerance mismatch effect depends on environmental context. These findings may help explain patterns of amphibian declines driven by a global wildlife pandemic.

Negative density dependence is stronger in resource‐rich environments and diversifies communities when stronger for common but not rare species - Joseph A. LaManna; Maranda L. Walton; Benjamin L. Turner; Jonathan A. Myers (Ecology Letters, 2016)
Conspecific negative density dependence is thought to maintain diversity by limiting abundances of common species. Yet the extent to which this mechanism can explain patterns of species diversity across environmental gradients is largely unknown. We examined density‐dependent recruitment of seedlings and saplings and changes in local species diversity across a soil‐resource gradient for 38 woody‐plant species in a temperate forest. At both life stages, the strength of negative density dependence increased with resource availability, becoming relatively stronger for rare species during seedling recruitment, but stronger for common species during sapling recruitment. Moreover, negative density dependence appeared to reduce diversity when stronger for rare than common species, but increase diversity when stronger for common species. Our results suggest that negative density dependence is stronger in resource‐rich environments and can either decrease or maintain diversity depending on its relative strength among common and rare species.

Geographical range in liverworts: does sex really matter? - Benjamin Laenen; Antonin Machac; S. Robbert Gradstein; Blanka Shaw; Jairo Patiño; Aurélie Désamoré; Bernard Goffinet; Cymon J. Cox; Jonathan Shaw; Alain Vanderpoorten (Journal of Biogeography, 2016)
Aim Why some species exhibit larger geographical ranges than others remains a fundamental, but largely unanswered, question in ecology and biogeography. In plants, a relationship between range size and mating system was proposed over a century ago and subsequently formalized in Baker's Law. Here, we take advantage of the extensive variation in sexual systems of liverworts to test the hypothesis that dioecious species compensate for limited fertilization by producing vegetative propagules more commonly than monoecious species. As spores are assumed to contribute to random long‐distance dispersal, whereas vegetative propagules contribute to colony maintenance and frequent short‐distance dispersal, we further test the hypothesis that monoecious species exhibit larger geographical ranges than dioecious ones. Location Worldwide. Methods We used comparative phylogenetic methods to assess the correlation between range size and life history traits related to dispersal, including mating systems, spore size and production of specialized vegetative propagules. Results No significant correlation was found between dioecy and production of vegetative propagules. However, production of vegetative propagules is correlated with the size of geographical ranges across the liverwort tree of life, whereas sexuality and spores size are not. Moreover, variation in sexual systems did not have an influence on the correlation between geographical range and production of asexual propagules. Main conclusions Our results challenge the long‐held notion that spores, and not vegetative propagules, are involved in long‐distance dispersal. Asexual reproduction seems to play a major role in shaping the global distribution patterns of liverworts, so that monoecious species do not tend to display, on average, broader distribution ranges than dioecious ones. Our results call for further investigation on the spatial genetic structure of bryophyte populations at different geographical scales depending on their mating systems to assess the dispersal capacities of spores and asexual propagules and determine their contribution in shaping species distribution ranges.

Targeted and untargeted lipidomics of Emiliania huxleyi viral infection and life cycle phases highlights molecular biomarkers of infection, susceptibility, and ploidy - Jonathan E. Hunter; Miguel J. Frada; Helen F. Fredricks; Assaf Vardi; Benjamin A. S. Van Mooy (Frontiers in Marine Science, 2015)

The cardiac safety of aripiprazole treatment in patients at high risk for torsade: a systematic review with a meta-analytic approach - Christoffer Polcwiartek; Benjamin Sneider; Claus Graff; David Taylor; Jonathan Meyer; Jørgen K. Kanters; Jimmi Nielsen (Psychopharmacology, 2015)

Endocannabinoid Catabolic Enzymes Play Differential Roles in Thermal Homeostasis in Response to Environmental or Immune Challenge - Sara R. Nass; Jonathan Z. Long; Joel E. Schlosburg; Benjamin F. Cravatt; Aron H. Lichtman; Steven G. Kinsey (Journal of Neuroimmune Pharmacology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

River of the dammed: longitudinal changes in fish assemblages in response to dams - Jonathan A. Freedman; Benjamin D. Lorson; Richard B. Taylor; Robert F. Carline; Jay R. Stauffer (Hydrobiologia, 2014)

High end GPCR design: crafted ligand design and druggability analysis using protein structure, lipophilic hotspots and explicit water networks - Jonathan S Mason; Andrea Bortolato; Dahlia R Weiss; Francesca Deflorian; Benjamin Tehan; Fiona H Marshall (In Silico Pharmacology, 2013)
Purpose G Protein-Coupled Receptors (GPCRs) are a large family of therapeutically important proteins and as diverse X-ray structures become available it is increasingly possible to leverage structural information for rational drug design. We present herein approaches that use explicit water networks combined with energetic surveys of the binding site (GRID), providing an enhanced druggability and ligand design approach, with structural understanding of ligand binding, including a ‘magic’ methyl and binding site mutations, and a fast new approach to generate and score waters. Methods The GRID program was used to identify lipophilic and hydrogen bonding hotspots. Explicit full water networks were generated and scored for (pseudo)apo structures and ligand-protein complexes using a new approach, WaterFLAP (Molecular Discovery), together with WaterMap (Schrödinger) for (pseudo)apo structures. A scoring function (MetaScore) was developed using a fast computational protocol based on several short adiabatic biased MD simulations followed by multiple short well-tempered metadynamics runs. Results Analysis of diverse ligands binding to the adenosine A 2A receptor together with new structures for the δ/κ/μ opioid and CCR5 receptors confirmed the key role of lipophilic hotspots in driving ligand binding and thus design; the displacement of ‘unhappy’ waters generally found in these regions provides a key binding energy component. Complete explicit water networks could be robustly generated for protein-ligand complexes using a WaterFLAP based approach. They provide a structural understanding of structure-activity relationships such as a ‘magic methyl’ effect and with the metadynamics approach a useful estimation of the binding energy changes resulting from active site mutations. Conclusions The promise of full structure-based drug design (SBDD) for GPCRs is now possible using a combination of advanced experimental and computational data. The conformational thermostabilisation of StaR® proteins provide the ability to easily generate biophysical screening data (binding including fragments, kinetics) and to get crystal structures with both potent and weak ligands. Explicit water networks for apo and ligand-complex structures are a critical ‘third dimension’ for SBDD and are key for understanding ligand binding energies and kinetics. GRID lipophilic hotspots are found to be key drivers for binding. In this context ‘high end’ GPCR ligand design is now enabled.

Survey of peanut levels in selected Irish food products bearing peanut allergen advisory labels - Orla N. Robertson; Jonathan O’B. Hourihane; Benjamin C. Remington; Joseph L. Baumert; Steve L. Taylor (Food Additives & Contaminants: Part A, 2013)

Soil microbial biomass and the fate of phosphorus during long-term ecosystem development - Benjamin L. Turner; Hans Lambers; Leo M. Condron; Michael D. Cramer; Jonathan R. Leake; Alan E. Richardson; Sally E. Smith (Plant and Soil, 2013)

Cyclodextrin-Crosslinked Poly(Acrylic Acid): Adhesion and Controlled Release of Diflunisal and Fluconazole from Solid Dosage Forms - Marguerite J. Kutyła; Michael W. Boehm; Jason R. Stokes; P. Nicholas Shaw; Nigel M. Davies; Ross P. McGeary; Jonathan Tuke; Benjamin P. Ross (AAPS PharmSciTech, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Cannabinol and cannabidiol exert opposing effects on rat feeding patterns - Jonathan A. Farrimond; Benjamin J. Whalley; Claire M. Williams (Psychopharmacology, 2012)

High site fidelity and low site connectivity in temperate salt marsh fish populations: a stable isotope approach - Benjamin C. Green; David J. Smith; Jonathan Grey; Graham J. C. Underwood (Oecologia, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Predicting phenology by integrating ecology, evolution and climate science - Stephanie Pau; Elizabeth M. Wolkovich; Benjamin I. Cook; T. Jonathan Davies; Nathan J. B. Kraft; Kjell Bolmgren; Julio L. Betancourt; Elsa E. Cleland (Global Change Biology, 2011)
Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology – the timing of life‐history events. Phenology has well‐demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on phenological responses to climate variability. Using insight into seasonal and interannual climate variability combined with niche theory and community phylogenetics, we develop a predictive approach for species’ reponses to changing climate. Our approach predicts that species occupying higher latitudes or the early growing season should be most sensitive to climate and have the most phylogenetically conserved phenologies. We further predict that temperate species will respond to climate change by shifting in time, while tropical species will respond by shifting space, or by evolving. Although we focus here on plant phenology, our approach is broadly applicable to ecological research of plant responses to climate variability.

An fMRI Study of the Differences in Brain Activity During Active Ankle Dorsiflexion and Plantarflexion - Jonathan P. Trinastic; Steven A. Kautz; Keith McGregor; Chris Gregory; Mark Bowden; Michelle B. Benjamin; Marc Kurtzman; Yu Ling Chang; Tim Conway; Bruce Crosson (Brain Imaging and Behavior, 2010)

Cannabis constituents modulate ∆9-tetrahydrocannabinol-induced hyperphagia in rats - Jonathan A. Farrimond; Andrew J. Hill; Benjamin J. Whalley; Claire M. Williams (Psychopharmacology, 2010)

Inhibitors of Endocannabinoid-Metabolizing Enzymes Reduce Precipitated Withdrawal Responses in THC-Dependent Mice - Joel E. Schlosburg; Brittany L. A. Carlson; Divya Ramesh; Rehab A. Abdullah; Jonathan Z. Long; Benjamin F. Cravatt; Aron H. Lichtman (The AAPS Journal, 2009)

Neuromuscular-skeletal constraints on the acquisition of skill in a discrete torque production task - Jonathan Shemmell; Matthew Forner; Benjamin Tathem; James R. Tresilian; Stephan Riek; Benjamin K. Barry; Richard G. Carson (Experimental Brain Research, 2006)

Predator effects on herbivore and plant stability - Benjamin S. Halpern; Elizabeth T. Borer; Eric W. Seabloom; Jonathan B. Shurin (Ecology Letters, 2005)
Humans are rapidly altering the diversity and composition of ecological communities by accelerating rates of species extinctions and introductions. These changes in diversity are not random and disproportionately involve the addition or extinction of predators. Theoretical and microcosm studies suggest predator removal may either increase or decrease ecosystem stability. Here we test whether the addition or removal of predators affects aggregate biomass stability in 40 experiments carried out in six different ecosystems. Predators did not alter the temporal variability of autotroph biomass, but significantly destabilized herbivore biomass. The effects of predators on herbivore biomass stability varied significantly among ecosystems, with benthic and pelagic lake systems showing the greatest shifts. Consequently, the addition of predators to communities, as occurs in many conservation efforts, biological control programmes and species introductions, may lead to more variable system dynamics.

Seaborne Petrochemical Spill Analysis Within the United States, 1992-1999 - BENJAMIN L. NICHOLSON; ANASTASSIOS N. PERAKIS; JONATHAN W. BULKLEY (Environmental Management, 2003)

A cross‐ecosystem comparison of the strength of trophic cascades - Jonathan B. Shurin; Elizabeth T. Borer; Eric W. Seabloom; Kurt Anderson; Carol A. Blanchette; Bernardo Broitman; Scott D. Cooper; Benjamin S. Halpern (Ecology Letters, 2002)
Although trophic cascades (indirect effects of predators on plants via herbivores) occur in a wide variety of food webs, the magnitudes of their effects are often quite variable. We compared the responses of herbivore and plant communities to predator manipulations in 102 field experiments in six different ecosystems: lentic (lake and pond), marine, and stream benthos, lentic and marine plankton, and terrestrial (grasslands and agricultural fields). Predator effects varied considerably among systems and were strongest in lentic and marine benthos and weakest in marine plankton and terrestrial food webs. Predator effects on herbivores were generally larger and more variable than on plants, suggesting that cascades often become attenuated at the plant–herbivore interface. Top‐down control of plant biomass was stronger in water than on land; however, the differences among the five aquatic food webs were as great as those between wet and dry systems.

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Microbiological, molecular biological and stable isotopic evidence for nitrogen fixation in the open waters of Lake Michigan - Barbara J. MacGregor; Benjamin Van Mooy; Brett J. Baker; Mark Mellon; Pia H. Moisander; Hans W. Paerl; Jonathan Zehr; David Hollander; David A. Stahl (Environmental Microbiology, 2001)
We have used a combination of microbiological, molecular biological and stable isotope methods to relate specific microbial populations to elemental cycling at an offshore site in Lake Michigan. Several lines of evidence suggest that atmospheric N 2 may be a significant source of nitrogen to the lake. Particulate organic nitrogen (PON) at ≈ 10–15 m depth in July and October had a δ 15 N of 0.5–1.5‰. These values closely reflect the 15 N composition of atmospheric N 2 , suggesting biological nitrogen fixation. Historical data show a developing late‐summer N:P minimum at ≈ 15 m; low abundance of inorganic nitrogen relative to phosphorus favours species able to acquire atmospheric nitrogen. Microscopic examination of October water samples revealed abundant heterocystous cyanobacteria, including Nodularia sp. Potentially nitrogen‐fixing Anabaena spp. have been found in Lake Michigan before but, to our knowledge, this is the first report of Nodularia . Finally, we have amplified both cyanobacterial and non‐cyanobacterial nifH sequences (encoding the nitrogenase iron protein) from lakewater samples, evidence for the presence of bacteria capable of nitrogen fixation. The surface waters of Lake Michigan are considered to be phosphate limited in the stratified season and, under these conditions, energetically expensive nitrogen fixation is expected to be uncompetitive with assimilation of combined nitrogen. Our results suggest that, from both microbiological and biogeochemical perspectives, this may be an oversimplification.

Delayed obsessive-compulsive disorder symptom exacerbation after a single dose of a serotonin antagonist in fluoxetine-treated but not untreated patients - B. D. Greenberg; Jonathan Benjamin; Juliet D. Martin; David Keuler; S.-J. Huang; Margaret Altemus; Dennis L. Murphy (Psychopharmacology, 1998)